Head-mounted display

CN116243494BActive Publication Date: 2026-10-09ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 28 Cites 0 Cited by

Patent Information

Application Number
CN202310364862.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-30
Filing Date
2020-04-28
Publication Date
2026-10-09
Estimated Expiration
2040-04-28

AI Technical Summary

Benefits of technology

[0026] According to the present invention, a resin light guide for a head-mounted display that can obtain clear images can be provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116243494B_ABST
    Figure CN116243494B_ABST
Patent Text Reader

Abstract

The object of this invention is to provide a resin light guide that enables clear images when used in a head-mounted display. The head-mounted display of this invention includes a resin light guide, characterized in that the average absolute value of the in-plane phase difference is less than 5 nm, and the content of the fluorescent luminescent substance, calculated using the concentration-intensity conversion formula of the fluorescein ethanol solution, is 0.1 × 10⁻⁶, based on the fluorescence intensity at 530 nm when a 2.0% by mass solution dissolved in chloroform is measured at an excitation wavelength of 436 nm. ‑9 ~4.0×10 ‑ 9 mol / L.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the application filed on April 28, 2020, with application number 202010349209.4 and invention title "Resin Light Guide for Head-Mounted Display". Technical Field

[0002] This invention relates to a head-mounted display. Background Technology

[0003] In recent years, various electronic technologies known as AR (Augmented Reality) have developed rapidly, and head-mounted display (HMD) products have become popular as their image display devices. As a perspective optical system used to superimpose image light and external light, a type of system has been proposed that guides image light from the display element into the observer's pupil through total internal reflection in the light guide body (Patent Documents 1-3).

[0004] On the other hand, head-mounted displays are image display devices worn on the head, thus requiring small size, light weight, and minimal discomfort during wear. Therefore, with the aim of reducing weight, attempts have been made to replace conventional glass light guides with resin. Resin light guides, compared to glass light guides, have a high coefficient of thermal expansion and low surface flatness, resulting in deterioration of image quality. Various solutions for improving image quality have been proposed to address this (Patent Documents 4-5).

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent document 1: Japanese Patent Application Publication No. 2007-94175.

[0008] Patent Document 2: Japanese Patent Publication No. 2008-535001.

[0009] Patent document 3: Japanese Patent Publication No. 2008-535032.

[0010] Patent document 4: Japanese Patent Application Publication No. 2017-173487.

[0011] Patent document 5: International Publication No. 2018 / 135193. Summary of the Invention

[0012] However, the inventors conducted research and confirmed that in head-mounted displays using resin light guides, it is not possible to obtain sufficiently clear images simply by addressing thermal expansion and flatness.

[0013] Therefore, the object of the present invention is to provide a resin light guide for a head-mounted display that obtains clear images.

[0014] In order to solve the above-mentioned problems, the inventors conducted in-depth research and found that in head-mounted displays with light guides formed using low birefringence resins, the content of fluorescent luminescent substances unexpectedly contained in the light guides affects the image clarity of the head-mounted display, thus completing the present invention.

[0015] That is, the present invention is as follows.

[0016] [1] A resin light guide for a head-mounted display, characterized in that...

[0017] The average absolute value of the in-plane phase difference is less than 5 nm.

[0018] Based on the fluorescence intensity at 530 nm when a 2.0% by mass solution dissolved in chloroform was measured at an excitation wavelength of 436 nm, the concentration-intensity conversion formula for the ethanol solution of fluorescein was used to determine the content of the fluorescent luminescent substance as 0.1 × 10⁻⁶. -9 ~4.0×10 -9 mol / L.

[0019] [2] The light guide for a head-mounted display according to [1] has a glass transition temperature Tg greater than 120°C and less than 160°C.

[0020] [3] A resin light guide for a head-mounted display according to [1] or [2], wherein the absolute value of the photoelastic coefficient is 3.0 × 10⁻⁶. -12 Pa -1 the following.

[0021] [4] A light guide for a head-mounted display made of resin according to any one of [1] to [3], wherein it comprises a methacrylic resin.

[0022] [5] The light guide for a head-mounted display according to [4], wherein the methacrylic resin comprises a methacrylic resin having a structural unit X, the structural unit X being a structural unit having a ring structure on the main chain.

[0023] [6] The resin light guide for a head-mounted display according to [5], wherein the structural unit X comprises at least one structural unit selected from the group consisting of structural units derived from N-substituted maleimide monomers, glutarimide structural units and lactone ring structural units.

[0024] [7] The resin light guide for a head-mounted display according to [5], wherein the structural unit X comprises a structural unit derived from an N-substituted maleimide monomer.

[0025] [8] The resin light guide for a head-mounted display according to [5], wherein the structural unit X comprises a glutarimide-based structural unit.

[0026] According to the present invention, a resin light guide for a head-mounted display that can obtain clear images can be provided. Attached Figure Description

[0027] Figure 1 This is a schematic diagram of an experimental system manufactured for evaluating the characteristics of a head-mounted display that uses the resin light guide for a head-mounted display according to the present invention in the embodiments.

[0028] The annotations in the attached figures are explained below.

[0029] 1: Display device; 2: Collimating lens; 3: Light guide; 4: First reflective volume hologram; 5: Second reflective volume hologram; 6: Pupil. Detailed Implementation

[0030] Hereinafter, this specific embodiment (hereinafter referred to as "this embodiment") will be described in detail, but the present invention is not limited to the following description and can be implemented in various modifications within its scope.

[0031] Resin light guide for head-mounted displays

[0032] The resin light guide for the head-mounted display of this embodiment is characterized in that the average absolute value of the in-plane phase difference of the light guide is less than 5 nm, and the content of the fluorescent luminescent substance, calculated using the concentration-intensity conversion formula of the fluorescein ethanol solution, is 0.1 × 10⁻⁶. This is based on the fluorescence intensity at a wavelength of 530 nm when a 2.0% by mass solution obtained by dissolving in chloroform is measured at an excitation wavelength of 436 nm. -9 ~4.0×10 -9 mol / L.

[0033] -In-plane phase difference of the light guide-

[0034] Regarding the resin light guide for the head-mounted display in this embodiment, the average absolute value of the in-plane phase difference of the light guide is 5 nm or less, preferably 4 nm or less, and more preferably 3 nm or less. Since the average absolute value of the phase difference is 5 nm or less, a head-mounted display providing a clear image can be obtained.

[0035] Here, the in-plane phase difference of the light guide is obtained by observing the surface containing the surface into which the image light is incident or the surface into which the display light is emitted, and specifically, it can be measured by the method described in the embodiments described later.

[0036] Although the reason for the image blurring when the absolute value of the in-plane phase difference of the light guide is large, i.e. when the birefringence of the light guide is high, is unclear, especially when a surface relief diffraction grating or a holographic diffraction grating is used on or opposite the incident part (incident surface) of the image light or on or opposite the emitting part (emission surface) of the display light, the diffraction efficiency depends on the orientation of the polarized light. Therefore, when light passes through a light guide with high birefringence by total internal reflection, if the polarization state changes, the polarization state will be different due to the difference in its optical path length, and spots will be generated in the emitted display light.

[0037] -Content of fluorescent luminescent substances-

[0038] Regarding the resin light guide for the head-mounted display in this embodiment, the fluorescence intensity at a wavelength of 530 nm, measured from a 2.0% by mass solution of the resin light guide obtained by dissolving the resin in chloroform at an excitation wavelength of 436 nm, was determined using the concentration-intensity conversion formula for the ethanol solution of fluorescein, and the content of the fluorescent luminescent substance was found to be 0.1 × 10⁻⁶. -9 ~4.0×10 -9 mol / L, preferably 0.2 × 10⁻⁶ mol / L. -9 ~3.5×10 -9 mol / L, more preferably 0.3×10 mol / L. -9 ~3.0×10 -9 mol / L, more preferably 0.3 × 10 mol / L. -9 ~2.5×10 -9 The concentration of the fluorescent luminescent substance is below the upper limit mentioned above, thereby obtaining images with high tonal reproduction, where the images can be clearly distinguished without blurring. Furthermore, the concentration of the fluorescent luminescent substance is above the lower limit mentioned above, thereby suppressing low-wavelength light harmful to the naked eye from entering the eye to the necessary level.

[0039] The reason why the image is blurred when the fluorescence intensity is high (the content of fluorescent luminescent material is high) is unclear, but it is presumed that when fluorescence is generated by light passing through the light guide, the light is also directed away from the original direction of light transmission, thus making the image blurred.

[0040] It should be noted that, regarding the content of fluorescent luminescent substances, when a hard coating or anti-reflective coating is applied to the surface of the resin light guide, the measurement is performed after removing these coatings. Specifically, the method described in the examples below can be used for measurement.

[0041] -Glass transition temperature-

[0042] In this embodiment, the glass transition temperature (Tg) of the resin light guide for the head-mounted display is preferably greater than 120°C and less than 160°C.

[0043] From the perspective of heat resistance to heat generation in head-mounted displays and the occurrence of photoelastic birefringence associated with dimensional changes, it is preferable that the glass transition temperature (Tg) of the resin light guide for head-mounted displays is greater than 120°C. From the perspective of dimensional stability under ambient temperature, the glass transition temperature (Tg) is more preferably 125°C or higher, and even more preferably 130°C or higher.

[0044] On the other hand, when the glass transition temperature (Tg) is below 160°C, melting processing at extremely high temperatures can be avoided, thermal decomposition of resins and the like can be suppressed, and a good product can be obtained. From the viewpoint of further obtaining the above-mentioned effects, the glass transition temperature (Tg) is preferably below 150°C, and more preferably below 140°C.

[0045] It should be noted that the glass transition temperature (Tg) can be determined according to JIS-K7121. Specifically, it can be determined using the method described in the examples below.

[0046] - Photoelasticity coefficient C R -

[0047] The photoelastic coefficient C of the resin light guide for the head-mounted display in this embodiment is... R absolute value | C R | Preferably 3.0×10 -12 Pa -1 Hereinafter, 2.0 × 10 is preferred. -12 Pa -1 The following is a further preferred value of 1.5 × 10⁻⁶. -12 Pa -1 Hereinafter, 1.0 × 10 is further preferred. -12 Pa -1 The photoelastic coefficient is described in various documents (e.g., see *General Chemistry*, No. 39, 1998 (published by the Society's Press Center)) and is defined by the following equations (ia) and (ib). It can be seen that the photoelastic coefficient C... R The closer the value is to zero, the smaller the change in birefringence due to external forces.

[0048] |C R |=|Δn| / σ R (ia)

[0049] |Δn|=|nx-ny| (ib)

[0050] (where C) R σ represents the photoelastic coefficient. R Let |Δn| represent the tensile stress, |Δn| represent the absolute value of birefringence, nx represent the refractive index in the tensile direction, and ny represent the refractive index in the in-plane direction perpendicular to the tensile direction.

[0051] As long as the photoelastic coefficient C of the resin photoconductive material in this embodiment is R absolute value | C R | is 3.0×10 -12 Pa -1 The following is a resin light guide that can obtain a sufficiently small stress generated when fixing the light guide, a photoelastic birefringence with changes in size and temperature, and a clear image.

[0052] It should be noted that regarding the photoelastic coefficient C... R The measurement is performed by finely cutting the resin light guide and then using a vacuum compression molding machine to form a pressed film. If a hard coating or anti-reflective coating is applied to the surface of the resin light guide, the coating is removed before measurement. Specifically, the result is obtained by the method described in the examples below.

[0053] -Light transmittance-

[0054] Regarding the resin light guide for the head-mounted display of this embodiment, for the transmittance in the thickest part measured using a spectrophotometer with a D65 light source and a 10° field of view, the ratio (T450 / T680) of the transmittance at wavelength 450 nm (T450) to the transmittance at wavelength 680 nm (T680) is preferably 0.95 to 1.03, more preferably 0.97 to 1.01, and even more preferably 0.98 to 1.00. If the ratio (T450 / T680) is within the above range, images with good tonal values ​​can be obtained.

[0055] It should be noted that, specifically, the transmittance can be measured using the method described in the examples below.

[0056] -Molecular weight and molecular weight distribution-

[0057] In this embodiment, the weight-average molecular weight (Mw) of the resin light guide for the head-mounted display, as determined by gel permeation chromatography (GPC), converted from polymethyl methacrylate, is preferably in the range of 80,000 to 170,000, more preferably in the range of 100,000 to 160,000, even more preferably in the range of 100,000 to 150,000, and even more preferably in the range of 120,000 to 150,000. If the weight-average molecular weight (Mw) is within the above range, the balance between mechanical strength and flowability is also excellent.

[0058] It should be noted that the weight-average molecular weight (Mw), number-average molecular weight (Mn), and Z-average molecular weight (Mz) of resin-based light guides can be measured using the following apparatus and conditions.

[0059] • Apparatus used for measurement: Gel permeation chromatography (HLC-8320GPC) manufactured by Tosoh Corporation.

[0060] The measurement conditions are as follows.

[0061] Chromatographic column: Connect one TSKguardcolumn SuperH-H, two TSKgel SuperHM-M, and one TSKgel SuperH2500 in series for use.

[0062] Column temperature: 40℃.

[0063] Developing solvent: tetrahydrofuran; flow rate: 0.6 mL / min; 2,6-di-tert-butyl-4-methylphenol (BHT) was added at 0.1 g / L as an internal standard.

[0064] Detector: RI (Differential Refraction) detector.

[0065] Detection sensitivity: 3.0 mV / min.

[0066] Sample: 20 mL solution of 0.02 g of a resin-based light guide in tetrahydrofuran.

[0067] Injection volume: 10 μL.

[0068] Standard samples for calibration curves: Ten polymethyl methacrylates (PMMA Calibration Kit MM-10) with known and different molecular weights and monodisperse gravimetric peaks were used.

[0069] Weight peak molecular weight (Mp)

[0070] Standard sample 2 625,500 Standard sample 3 298,900 Standard sample 4 138,600 Standard sample 5 60,150 Standard sample 6 27,600 Standard sample 7 10,290 Standard sample 8 5,000 Standard sample 9 2,810 Standard sample 10 850

[0071] Under the above conditions, the RI detection intensity relative to the elution time of the resin-based light guide was measured.

[0072] Based on the calibration curves obtained by measuring standard samples, the weight-average molecular weight (Mw), number-average molecular weight (Mn), and Z-average molecular weight (Mz) of the resin-based light guide were determined, and their values ​​were used to determine the molecular weight distribution (Mw / Mn) and (Mz / Mw). It should be noted that when a hard coating or anti-reflective coating is applied to the surface of the resin-based light guide, these coatings are removed before the measurements are performed.

[0073] -Methanol-insoluble components-

[0074] In this embodiment, the amount of methanol-insoluble component in the resin light guide for the head-mounted display is preferably 95% by mass or more, more preferably 95.5% by mass or more, further preferably 96% by mass or more, even more preferably 96.5% by mass or more, particularly preferably 97% by mass or more, and most preferably 97.5% by mass or more, relative to 100% by mass of the total amount of methanol-insoluble component and methanol-soluble component. By setting the proportion of methanol-insoluble component to 95% by mass or more, molding problems such as silver streaks during injection molding can be suppressed.

[0075] It should be noted that methanol-insoluble and methanol-soluble components refer to the components obtained by dissolving a resin light guide for a head-mounted display in chloroform to prepare a chloroform solution, then adding the solution dropwise to a large excess of methanol to induce reprecipitation, separating the filtrate and residue, and subsequently drying each component. In cases where a hard coating or anti-reflective coating is applied to the surface of the resin light guide, these coatings are removed before measurement.

[0076] Specifically, the following steps can be taken: Dissolve 5g of the resin-based light guide in 100mL of chloroform. Add the solution to a dropping funnel and dropwise over approximately 1 hour to 1L of methanol stirred with a stir bar for reprecipitation. After the entire volume has been added, allow it to stand for 1 hour. Then, use a membrane filter (manufactured by Advantech Toyo Co., Ltd., T050A090C) for suction filtration. Dry the filter residue under vacuum at 60°C for 16 hours to obtain the methanol-insoluble component. Regarding the filtrate, set the rotary evaporator bath temperature to 40°C, gradually decrease the vacuum from the initial setting of 390 Torr to a final setting of 30 Torr, remove the solvent, and recover the soluble component remaining in the flask as the methanol-soluble component. Weigh the mass of the methanol-insoluble component and the mass of the methanol-soluble component, and calculate the ratio (mass%) of the amount of methanol-soluble component to the total amount of methanol-insoluble component (100% by mass) (methanol-soluble component rate).

[0077] [Resin Composition]

[0078] The resin light guide for the head-mounted display in this embodiment is preferably composed of a resin composition containing a methacrylic resin.

[0079] [Methacrylic resins]

[0080] The methacrylic resin included in the light guide for the head-mounted display of this embodiment preferably comprises a methacrylic resin having structural units X having a ring structure on the main chain and structural units derived from methacrylate monomers. By including a methacrylic resin, and particularly a methacrylic resin having structural units X having a ring structure on the main chain and methacrylate monomer units, a resin light guide with sufficiently small in-plane phase difference and sufficiently small photoelastic coefficient can be obtained.

[0081] The following is a description of each structural unit.

[0082] -Structural units derived from methacrylate monomers-

[0083] As structural units derived from methacrylate monomers, examples include structural units derived from monomers selected from the following methacrylate classes. Examples of methacrylates include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, 2-ethylhexyl methacrylate, cyclopentyl methacrylate, cyclohexyl methacrylate, cyclooctyl methacrylate, tricyclodecyl methacrylate, dicyclooctyl methacrylate, tricyclododecyl methacrylate, isobornyl methacrylate, phenyl methacrylate, benzyl methacrylate, 1-phenylethyl methacrylate, 2-phenoxyethyl methacrylate, 3-phenylpropyl methacrylate, and 2,4,6-tribromophenyl methacrylate.

[0084] These monomers are sometimes used alone, and sometimes two or more are used together.

[0085] From the perspective of the excellent transparency and weather resistance of the obtained methacrylate resin, structural units derived from methyl methacrylate and benzyl methacrylate are preferred as structural units derived from the above-mentioned methacrylate monomers.

[0086] The structural units derived from methacrylate monomers can contain one or more types.

[0087] The resin light guide for a head-mounted display according to this embodiment reduces birefringence caused by orientation and residual stress during molding by appropriately adjusting the ratio of structural units X with ring structures on the main chain to structural units derived from methacrylate monomers. This results in a resin light guide with an average absolute value of in-plane phase difference of less than 5 nm. Furthermore, by appropriately adjusting the aforementioned ratio, sufficient heat resistance can be imparted to the methacrylate resin. From these viewpoints, the content of structural units derived from methacrylate monomers, based on 100% by mass of the methacrylate resin, is preferably 50–97% by mass, more preferably 55–97% by mass, even more preferably 55–95% by mass, even more preferably 60–93% by mass, and particularly preferably 60–90% by mass.

[0088] It should be noted that the content of structural units derived from methacrylate monomers can be determined by... 1 H-NMR measurements and 13 The result can be determined by C-NMR measurement. For example, CDCl3 or DMSO-d6 can be used as the measurement solvent, and the measurement can be performed at a temperature of 40°C. 1 H-NMR measurements and 13 C-NMR determination.

[0089] The following describes the structural unit X with a ring structure on the main chain.

[0090] The structural unit X having a ring structure on the main chain preferably comprises at least one structural unit selected from the group consisting of structural units derived from N-substituted maleimide monomers, glutarimide-based structural units, and lactone ring structural units. More preferably, it is composed solely of at least one structural unit selected from the group consisting of structural units derived from N-substituted maleimide monomers, glutarimide-based structural units, and lactone ring structural units. The structural unit X having a ring structure on the main chain can be one type or a combination of multiple types.

[0091] -Structural units derived from N-substituted maleimide monomers-

[0092] Next, the structural units derived from N-substituted maleimide monomers will be described.

[0093] The structural unit derived from the N-substituted maleimide monomer can be at least one structural unit selected from the group consisting of structural units represented by formula (1) and structural units represented by formula (2) below. Preferably, it is formed by two structural units represented by formula (1) and formula (2) below.

[0094] [Chemical Formula 1]

[0095]

[0096] In equation (1), R 1 R represents either an arylalkyl group having 7 to 14 carbon atoms or an aryl group having 6 to 14 carbon atoms. 2 and R 3 Each of the following can be independently represented: a hydrogen atom, an oxygen atom, a sulfur atom, an alkyl group having 1 to 12 carbon atoms, or an aryl group having 6 to 14 carbon atoms.

[0097] Additionally, in R 2 or R 3 In the case of aryl, R 2 or R 3 It can be used as a substituent to contain halogen atoms.

[0098] Additionally, R 1 It can be substituted by halogen atoms, alkyl groups with 1 to 6 carbon atoms, alkoxy groups with 1 to 6 carbon atoms, nitro groups, benzyl groups, etc.

[0099] [Chemical Formula 2]

[0100]

[0101] In equation (2), R 4 R represents any one of hydrogen atoms, cycloalkyl groups having 3 to 12 carbon atoms, or alkyl groups having 1 to 12 carbon atoms. 5 and R 6 Each of the following can be independently represented: a hydrogen atom, an oxygen atom, a sulfur atom, an alkyl group having 1 to 12 carbon atoms, or an aryl group having 6 to 14 carbon atoms.

[0102] The following are specific examples.

[0103] As monomers forming the structural unit represented by formula (1) (N-arylmaleimides, N-aromatic substituted maleimides, etc.), examples include N-phenylmaleimide, N-benzylmaleimide, N-(2-chlorophenyl)maleimide, N-(4-chlorophenyl)maleimide, N-(4-bromophenyl)maleimide, N-(2-methylphenyl)maleimide, N-(2,6-dimethylphenyl)maleimide, N-(2-ethylphenyl)maleimide, N-(2-methoxyphenyl)maleimide, N-(2-nitrophenyl)maleimide, N-(2,4,6-trimethylphenyl)maleimide, N-(4-benzylphenyl)maleimide, N-(2,4,6-tribromophenyl)maleimide, N-naphthylmaleimide, N-anthraylmaleimide, 3-methyl-1-phenyl-1H-pyrrole-2,5-dione, 3,4-dimethyl-1-phenyl-1H-pyrrole-2,5-dione, 1,3-diphenyl-1H-pyrrole-2,5-dione, 1,3,4-triphenyl-1H-pyrrole-2,5-dione, etc.

[0104] Among these monomers, N-phenylmaleimide and N-benzylmaleimide are preferred, considering the excellent heat resistance and optical properties such as birefringence of the obtained methacrylic resins.

[0105] These monomers are sometimes used alone, and sometimes two or more are used together.

[0106] Examples of monomers that form the structural unit represented by formula (2) include, for example, N-methylmaleimide, N-ethylmaleimide, N-n-propylmaleimide, N-isopropylmaleimide, N-n-butylmaleimide, N-isobutylmaleimide, N-sec-butylmaleimide, N-tert-butylmaleimide, N-n-pentylmaleimide, N-n-hexylmaleimide, and N-n-heptylmaleimide. N-octylmaleimide, N-laurylmaleimide, N-cyclopentylmaleimide, N-cyclohexylmaleimide, 1-cyclohexyl-3-methyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3,4-dimethyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3-phenyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3,4-diphenyl-1H-pyrrole-2,5-dione, etc.

[0107] Among these monomers, N-methylmaleimide, N-ethylmaleimide, N-isopropylmaleimide, and N-cyclohexylmaleimide are preferred from the perspective of the excellent weather resistance of methacrylic resins. From the perspective of the excellent low moisture absorption required by optical materials in recent years, N-cyclohexylmaleimide is particularly preferred.

[0108] These monomers can sometimes be used alone, or two or more can be used together.

[0109] In the methacrylic resin of this embodiment, it is particularly preferred to use a combination of structural units represented by formula (1) and structural units represented by formula (2) in order to exhibit highly controllable birefringence characteristics.

[0110] The molar ratio (X1 / X2) of the content of the structural unit (X1) represented by Equation (1) to the content of the structural unit (X2) represented by Equation (2) is preferably greater than 0 and less than 15, and more preferably greater than 0 and less than 10.

[0111] When the molar ratio (X1 / X2) is within this range, the resin-based light guide of this embodiment maintains transparency without yellowing and does not impair environmental resistance, exhibiting good heat resistance and good photoelastic properties.

[0112] The content of structural units derived from N-substituted maleimide monomers, based on 100% by mass of methacrylic resin, is preferably in the range of 5 to 40% by mass, and more preferably in the range of 5 to 35% by mass.

[0113] Within this range, methacrylic resins achieve a more substantial improvement in heat resistance, and further improvements in weather resistance, low water absorption, and optical properties. It should be noted that, to prevent a decrease in the physical properties of methacrylic resins due to reduced reactivity of monomer components and an increase in the amount of unreacted and residual monomers during polymerization, it is effective to set the content of structural units derived from N-substituted maleimide monomers to 40% by mass or less.

[0114] Furthermore, by appropriately adjusting the content of structural units derived from N-substituted maleimide monomers within this range, birefringence caused by orientation and residual stress during molding can be reduced, enabling the acquisition of resin light guides for head-mounted displays with an average absolute value of in-plane phase difference of less than 5 nm. The most suitable content of structural units derived from N-substituted maleimide monomers varies depending on the type of N-substituted maleimide. For example, when methyl methacrylate is used as a methacrylate monomer, and N-phenylmaleimide and N-cyclohexylmaleimide are used as N-substituted maleimide monomers, it is preferable to adjust the content within the range of 79–83% by mass of structural units derived from methyl methacrylate, 6–8% by mass of structural units derived from N-phenylmaleimide, and 11–13% by mass of structural units derived from N-cyclohexylmaleimide.

[0115] Without prejudice to the purpose of the present invention, the methacrylic resin constituting the light guide of the head-mounted display, having structural units derived from N-substituted maleimide monomers, may contain structural units derived from other monomers that can be copolymerized with methacrylate monomers and N-substituted maleimide monomers.

[0116] For example, other monomers that can be copolymerized as described above include aromatic vinyl groups; unsaturated nitrile groups; acrylates having cyclohexyl, benzyl, or alkyl groups having 1 to 18 carbon atoms; glycidyl compounds; unsaturated carboxylic acids; etc.

[0117] Examples of aromatic vinyl groups include styrene, α-methylstyrene, and divinylbenzene.

[0118] Examples of unsaturated nitriles include acrylonitrile, methacrylonitrile, and ethyl acrylonitrile.

[0119] Examples of acrylates mentioned above include methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, and butyl acrylate.

[0120] Examples of glycidyl compounds mentioned above include glycidyl (meth)acrylate.

[0121] Examples of unsaturated carboxylic acids include acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, and their semi-esterified or anhydrides.

[0122] The aforementioned copolymerizable structural units derived from other monomers may be of only one type or of two or more types.

[0123] The content of these copolymerizable structural units derived from other monomers, based on 100% by mass of methacrylic resin, is preferably 0 to 10% by mass, more preferably 0 to 9% by mass, and even more preferably 0 to 8% by mass.

[0124] When the content of structural units derived from other monomers is within this range, it can improve the molding processability and mechanical properties of the resin without compromising the original effect of the introduced ring structure on the main chain, and is therefore preferred.

[0125] It should be noted that the content of structural units derived from N-substituted maleimide monomers and the content of structural units derived from other copolymerizable monomers can be determined by... 1 H-NMR measurements and 13 The result can be determined by C-NMR measurement. For example, CDCl3 or DMSO-d6 can be used as the measurement solvent, and the measurement can be performed at a temperature of 40°C. 1 H-NMR measurements and 13 C-NMR determination.

[0126] -Glutarimide structural unit-

[0127] As a methacrylic resin having glutarimide structural units on its main chain, examples of methacrylic resins having glutarimide structural units described in Japanese Patent Application Publication Nos. 2006-249202, 2007-009182, 2007-009191, 2011-186482, and 2012 / 114718 can be formed by the methods described in those publications.

[0128] The glutarimide structural unit constituting the methacrylic resin in this embodiment can be formed after resin polymerization.

[0129] Specifically, the glutarimide structural unit can be a substance represented by the following general formula (3).

[0130] [Chemical Formula 3]

[0131]

[0132] In the above general formula (3), it is preferred that R 7 and R 8 Each can be independently a hydrogen atom or a methyl group, R 9 It can be any one of hydrogen atom, methyl, butyl, or cyclohexyl, more preferably, R 7 It is methyl, R 8 For hydrogen atoms, R 9 It is a methyl group.

[0133] Glutarimide structural units can contain either a single type or multiple types.

[0134] In methacrylic resins having glutarimide structural units, the content of glutarimide structural units, based on 100% by mass of methacrylic resin, is preferably in the range of 3 to 70% by mass, more preferably in the range of 3 to 60% by mass.

[0135] When the content of glutarimide structural units is within the above range, a resin with good molding processability, heat resistance and optical properties can be obtained, and therefore it is preferred.

[0136] Furthermore, by appropriately adjusting the content of glutarimide-based structural units within this range, and reducing birefringence caused by orientation and residual stress during molding, it is possible to obtain a resin light guide for head-mounted displays with an average absolute value of less than 5 nm for the in-plane phase difference. The optimal content of glutarimide-based structural units depends on R in general formula (3). 7 ~R9 It varies depending on the type of substituent, for example, in R 7 and R 8 For hydrogen atoms, R 9 When the content of the glutarimide structural unit is 3 to 10% by mass, the birefringence caused by orientation and residual stress during molding is reduced, and a resin light guide for head-mounted displays with an average absolute value of less than 5 nm in the in-plane phase difference can be obtained.

[0137] It should be noted that the content of glutarimide structural units in methacrylic resins can be determined using the methods described in the aforementioned patent documents.

[0138] As needed, methacrylic resins having glutarimide-based structural units may further include aromatic vinyl monomer units.

[0139] There are no particular limitations on aromatic vinyl monomers; examples include styrene and α-methylstyrene, with styrene being the preferred choice.

[0140] The content of aromatic vinyl units in methacrylic resins having glutarimide structural units is not particularly limited, but is preferably 0 to 20% by mass, based on 100% by mass of methacrylic resins having glutarimide structural units.

[0141] When the content of aromatic vinyl units is within the above range, it can combine heat resistance and excellent photoelastic properties, and is therefore preferred.

[0142] For example, when a resin is obtained by copolymerizing methyl methacrylate as a methyl methacrylate monomer and styrene as an aromatic vinyl monomer with glutarimide, by adjusting the methyl methacrylate-styrene copolymer to a range of 65-90% by mass, styrene-derived structural units to 5-15% by mass, and glutarimide-based structural units to 5-20% by mass, birefringence caused by orientation and residual stress during molding can be reduced, and a resin light guide for head-mounted displays with an average absolute value of less than 5 nm for the in-plane phase difference can be obtained.

[0143] -Lactone ring structural unit-

[0144] Methacrylic acid resins having lactone ring structural units on the main chain can be formed, for example, by the methods described in Japanese Patent Application Publication Nos. 2001-151814, 2004-168882, 2005-146084, 2006-96960, 2006-171464, 2007-63541, 2007-297620, and 2010-180305.

[0145] The lactone ring structural unit constituting the methacrylic resin in this embodiment can be formed after resin polymerization.

[0146] As the lactone ring structural unit in this embodiment, a six-membered ring is preferred from the perspective of excellent ring structure stability.

[0147] As a six-membered ring lactone ring structural unit, for example, the structure represented by the following general formula (4) is particularly preferred.

[0148] [Chemical Formula 4]

[0149]

[0150] In the above general formula (4), R 10 R 11 and R 12 Organic residues consisting of 1 to 20 hydrogen or carbon atoms, which are independent of each other.

[0151] Examples of organic residues include, for example, saturated aliphatic hydrocarbon groups (alkyl, etc.) with 1 to 20 carbon atoms such as methyl, ethyl, and propyl; unsaturated aliphatic hydrocarbon groups (alkenyl, etc.) with 2 to 20 carbon atoms such as vinyl and propenyl; aromatic hydrocarbon groups (aryl, etc.) with 6 to 20 carbon atoms such as phenyl and naphthyl; groups formed by replacing one or more hydrogen atoms of these saturated aliphatic hydrocarbon groups, unsaturated aliphatic hydrocarbon groups, and aromatic hydrocarbon groups with at least one group selected from the group consisting of hydroxyl, carboxyl, ether, and ester groups; etc.

[0152] For example, by copolymerizing acrylic monomers with hydroxyl groups with methacrylate monomers such as methyl methacrylate to introduce hydroxyl and ester or carboxyl groups into the molecular chain, de-alcoholization (esterification) or dehydration condensation (hereinafter also referred to as "cyclization condensation reaction") occurs between these hydroxyl and ester or carboxyl groups, thereby forming lactone ring structural units.

[0153] Examples of hydroxyl-containing acrylic monomers used in polymerization include 2-(hydroxymethyl)acrylic acid, 2-(hydroxyethyl)acrylic acid, alkyl 2-(hydroxymethyl)acrylates (e.g., methyl 2-(hydroxymethyl)acrylate, ethyl 2-(hydroxymethyl)acrylate, isopropyl 2-(hydroxymethyl)acrylate, n-butyl 2-(hydroxymethyl)acrylate, tert-butyl 2-(hydroxymethyl)acrylate), and alkyl 2-(hydroxyethyl)acrylates. Monomers having a hydroxyalkyl group, namely 2-(hydroxymethyl)acrylic acid and alkyl 2-(hydroxymethyl)acrylates, are preferred, and methyl 2-(hydroxymethyl)acrylate and ethyl 2-(hydroxymethyl)acrylates are particularly preferred.

[0154] The content of lactone ring structural units in methacrylic resins having lactone ring structural units on the main chain is preferably 5 to 40% by mass, more preferably 5 to 35% by mass, relative to 100% by mass of the methacrylic resin.

[0155] When the content of lactone ring structural units is within this range, the ring structure introduction effect, such as improved solvent resistance and increased surface hardness, can be achieved while maintaining molding processability. In addition, by appropriately adjusting the content of lactone ring structural units within this range, the birefringence caused by orientation and residual stress during molding can be reduced, and resin light guides for head-mounted displays with an average absolute value of in-plane phase difference of less than 5 nm can be obtained.

[0156] It should be noted that the content of lactone ring structures in methacrylic resins can be determined using the methods described in the aforementioned patent documents.

[0157] Methacrylic resins with lactone ring structural units on the main chain can have structural units derived from other monomers that can copolymerize with the aforementioned methacrylic ester monomers and acrylic monomers with hydroxyl groups.

[0158] Other monomers that can be copolymerized include, for example, styrene, vinyltoluene, α-methylstyrene, α-hydroxymethylstyrene, α-hydroxyethylstyrene, acrylonitrile, methacrylonitrile, methyl allyl alcohol, ethylene, propylene, 4-methyl-1-pentene, vinyl acetate, 2-hydroxymethyl-1-butene, methyl vinyl ketone, N-vinylpyrrolidone, N-vinylcarbazole, and other monomers with polymerizable double bonds.

[0159] These other monomers (constituent units) may have only one type or more than two types.

[0160] The content of these structural units derived from other copolymerizable monomers is preferably 0 to 20% by mass relative to 100% by mass of the methacrylate resin, more preferably less than 10% by mass from the viewpoint of weather resistance, and even more preferably less than 7% by mass.

[0161] The methacrylic resin in this embodiment may have only one of the above-mentioned structural units derived from other copolymerizable monomers, or it may have two or more of the above-mentioned structural units derived from other copolymerizable monomers.

[0162] The methacrylic resin in this embodiment preferably has at least one structural unit selected from the group consisting of structural units derived from N-substituted maleimide monomers, glutarimide structural units, and lactone ring structural units. In particular, structural units derived from N-substituted maleimide monomers are preferred from the viewpoint of easily and effectively controlling optical properties such as the photoelasticity coefficient without mixing with other thermoplastic resins. Furthermore, structural units comprising glutarimide structural units are particularly preferred from the viewpoint of obtaining high-strength resin-based light guides.

[0163] [Manufacturing method of methacrylic resins]

[0164] The method for manufacturing the methacrylic resin of this embodiment will be described below.

[0165] - Method for manufacturing methacrylic resins containing structural units derived from N-substituted maleimide monomers-

[0166] As a method for manufacturing methacrylic resins (hereinafter, sometimes referred to as "maleimide copolymers") having structural units derived from N-substituted maleimide monomers on the main chain, any polymerization method such as bulk polymerization, solution polymerization, suspension polymerization, precipitation polymerization, and emulsion polymerization can be cited. From the viewpoint of reducing the amount of residual monomers and impurities contained in the resin photoconductor, suspension polymerization, bulk polymerization, and solution polymerization are preferred, and solution polymerization is more preferred.

[0167] In the manufacturing method of this embodiment, as a polymerization method, for example, any one of batch polymerization, semi-batch polymerization, or continuous polymerization can be used.

[0168] In this embodiment, from the viewpoint of reducing the amount of residual maleimide at the end of polymerization and reducing fluorescence intensity (reducing the content of fluorescent luminescent substances), it is preferable to use a so-called semi-batch polymerization method, which is a method in which a portion of the monomer is loaded into the reactor before polymerization begins, polymerization is started by adding a polymerization initiator, and then the remaining portion of the monomer is supplied.

[0169] In methacrylic resins having structural units derived from N-substituted maleimide monomers, methods for controlling the fluorescence intensity (the content of the fluorescent substance within a specified range) of the obtained resin-made light guide can be exemplified by performing at least one of (1) to (3): (1) using an N-substituted maleimide monomer as a raw material with controlled content of specific impurities; (2) a polymerization method that reduces the amount of unreacted N-substituted maleimide remaining after polymerization; and (3) a devolatilization method that reduces shear. Preferably, a manufacturing method combining (1) and (3) or a manufacturing method combining all three is selected.

[0170] (1) Control of impurities in N-substituted maleimides

[0171] As an impurity in N-substituted maleimides that provide fluorescence to methacrylic resins, 2-amino-N-substituted succinimides, which are produced by the reaction of N-substituted maleimides with primary amines, can be cited as examples. Examples of 2-amino-N-substituted succinimides include 2-cyclohexylamino-N-cyclohexylsuccinimides and 2-anilino-N-phenylsuccinimides. 2-amino-N-substituted succinimides not only possess fluorescence themselves, but through the inventors' research, it has been clarified that although the detailed modification mechanism is unclear, heating them above 300°C or feeding them into a devolatilization device with shearing properties produces a thermally modified product with fluorescence. That is, in order to control the fluorescence intensity of methacrylic resins and the resulting resin-based light guides, it is preferable to reduce the amount of 2-amino-N-substituted succinimides contained in the N-substituted maleimides and to use a devolatilization device without a rotating part in the manufacture of methacrylic resins and to perform devolatilization at temperatures below 300°C.

[0172] As a method for controlling impurities in N-substituted maleimides, examples include setting up pretreatment steps such as washing the N-substituted maleimides with water (water washing step) and / or dehydrating them (dehydration step).

[0173] The aforementioned pretreatment step can be either water washing alone or a combination of water washing and dehydration. Furthermore, water washing and dehydration can be performed once each, or more than twice. In the aforementioned pretreatment step, a concentration adjustment step can be further included to adjust the concentration of the N-substituted maleimide solution obtained from the dehydration step.

[0174] In this embodiment, for example, 2-amino-N-substituted succinimide in N-substituted maleimide is removed by a water washing step as shown below, followed by water removal in a dehydration step, thereby obtaining an N-substituted maleimide solution suitable for preparing methacrylic resins with controlled fluorescence intensity and good hue.

[0175] In the washing process, for example, the following method can be used: dissolve N-substituted maleimide in a non-water-soluble organic solvent, separate it into an organic layer and an aqueous layer, and then use one or more liquids, namely acidic aqueous solution, water, and alkaline aqueous solution, to mix and wash the organic layer in a stepwise, continuous or both manner, and then separate the organic layer and the aqueous layer.

[0176] When the amount of N-substituted maleimide in the organic layer is set to 100% by mass, the amount of 2-amino-N-substituted succinimide in the organic layer after the water washing process is preferably 5 ppm by mass or less, more preferably 0.1 ppm by mass or more or 1 ppm by mass. When the amount of 2-amino-N-substituted succinimide in the organic layer is within this range, the concentration of fluorescent light-emitting substances in the methacrylic resin and the obtained resin-based light guide can be controlled within the above range, and a resin-based light guide for a head-mounted display that can obtain clear images can be obtained, which is therefore preferred. In addition, it is also preferred from the perspective of cost in cleaning. In the absence of a dehydration process, the organic layer containing N-substituted maleimide obtained in the water washing process can be used as an N-substituted maleimide solution in the polymerization process.

[0177] It should be noted that the amount of 2-amino-N-substituted succinimide in the organic layer can be determined, for example, by using isopropyl benzoate as an internal standard substance and measuring it by gas chromatography, liquid chromatography, etc. Specifically, it can be determined by the method described in the examples below.

[0178] There are no particular restrictions on the non-water-soluble organic solvents used, as long as they can dissolve N-substituted maleimide and 2-amino-N-substituted succinimide, allow phase separation from water, and have an azeotropic point with water. Specifically, for example, aromatic hydrocarbons such as toluene and xylene; aliphatic hydrocarbons such as n-hexane and cyclohexane; halogenated hydrocarbons such as chloroform and dichloroethane; etc.

[0179] The water used can be any type of wastewater, pure water, or tap water.

[0180] In addition, there are no particular restrictions on the acidity of acidic and alkaline aqueous solutions.

[0181] The concentration of N-substituted maleimide in the organic layer before the water washing process is preferably 0.5% by mass or more and 30% by mass or less, more preferably 10% by mass or more and 25% by mass or less, and even more preferably 20% by mass or more and 25% by mass or less.

[0182] The temperature for mixing and cleaning the organic layer and the water layer can be above 40°C, preferably above 40°C and below 80°C, and more preferably above 50°C and below 60°C.

[0183] When the mass of the organic layer is set to 100% by mass, the mass ratio of the water layer to the organic layer is preferably 5% by mass or more and 300% by mass or less, more preferably 10% by mass or more and 200% by mass, and even more preferably 30% by mass or more and 100% by mass or less.

[0184] When the concentration of N-substituted maleimide in the organic layer, the liquid temperature during washing, and the mass ratio of the water layer are within these ranges, the reaction between N-substituted maleimide and water is difficult to proceed, and 2-amino-N-substituted succinimide is easily extracted to the water layer side, which is therefore preferred.

[0185] When cleaning is performed in stages, the reaction tank can be made of stainless steel, glass, or any other material. Furthermore, there are no particular restrictions on the shape of the agitator blades. Specific agitator blades include, for example, three swept blades, four paddle blades, four tilting paddle blades, six turbine blades, and anchor blades. Additionally, the Twin Star and Full Zone agitators manufactured by Kobe Steel Environmental Solutions can also be used.

[0186] The stirring time is preferably 10 to 120 minutes, more preferably 30 to 60 minutes. Regarding the stirring speed, it is appropriate to select a speed that results in a turbulent mixture without emulsification. When the stirring time and speed are within these ranges, the stirring efficiency and the extraction efficiency of 2-amino-N-substituted succinimide into the aqueous layer can be improved, and the 2-amino-N-substituted succinimide in N-substituted maleimide can be further reduced, therefore this is preferred.

[0187] When cleaning is performed continuously, empty towers, filled towers, or plate towers can be used, as well as static mixers such as static mixers and rotary mixers such as dynamic mixers.

[0188] The contact time between the organic layer and the aqueous layer is preferably set to 1 second to 60 minutes, more preferably 30 seconds to 10 minutes. When the contact time is within this range, the reaction between N-substituted maleimide and water is difficult to proceed, and 2-amino-N-substituted succinimide is easily extracted to the aqueous layer side, which is therefore preferred.

[0189] In the dehydration process, an organic layer is supplied to the reaction tank, and water is removed by heating under reduced pressure. There are no particular restrictions on pressure and temperature, as long as the solvent and water form an azeotropic mixture.

[0190] The moisture content in the organic layer after the dehydration process is preferably below 100 ppm, assuming the mass of the organic layer is 100% by mass. When the moisture content after the dehydration process is within this range, the color deterioration caused by water during the polymerization of methacrylic resins can be suppressed, and the amount of solvent removed by distillation along with water can be reduced. Therefore, it is also preferred from a cost perspective.

[0191] The organic layer containing N-substituted maleimide obtained from the dehydration process can be used as an N-substituted maleimide solution in the polymerization process. Alternatively, the N-substituted maleimide solution whose concentration has been adjusted in the concentration adjustment process can also be used in the polymerization process.

[0192] In the concentration adjustment process, for example, the organic layer of the N-substituted maleimide obtained from the dehydration process can be diluted with the aforementioned water-insoluble organic solvent. The water-insoluble organic solvent used in the concentration adjustment process is preferably the same as the water-insoluble organic solvent used in the washing process.

[0193] The N-substituted maleimide solution obtained from the above pretreatment process is preferably a solution (organic layer) of the above-mentioned non-water-soluble organic solvent.

[0194] The N-substituted maleimide solution obtained from the above pretreatment process preferably contains 5 ppm or less, and more preferably 0.1 ppm or more or 1 ppm or less, relative to 100% by mass of N-substituted maleimide contained in the above N-substituted maleimide solution and the mass ratio of 2-amino-N-substituted succinimide contained in the above N-substituted maleimide solution.

[0195] The water content in the N-substituted maleimide solution obtained from the above pretreatment process is preferably 200 ppm or less, more preferably 100 to 200 ppm, relative to 100% by mass of the N-substituted maleimide solution.

[0196] The mass percentage of N-substituted maleimide in the N-substituted maleimide solution obtained from the above pretreatment process is preferably 5 to 30% by mass, more preferably 5 to 25% by mass, relative to 100% by mass of the N-substituted maleimide solution. Within this range, the N-substituted maleimide is difficult to precipitate and can be transported in a homogeneous solution manner, which is therefore preferred.

[0197] When multiple N-substituted maleimide solutions are used in the polymerization process, it is preferable that the mixture of multiple N-substituted maleimide solutions satisfies the above-mentioned mass ratio of 2-amino-N-substituted succinimide, the above-mentioned moisture content, and / or the above-mentioned mass ratio of N-substituted maleimide. More preferably, each N-substituted maleimide solution satisfies the above-mentioned mass ratio of 2-amino-N-substituted succinimide, the above-mentioned moisture content, and / or the above-mentioned mass ratio of N-substituted maleimide.

[0198] By employing the washing and dehydration processes of N-substituted maleimide as described above, it is possible to reduce the amount of 2-amino-N-substituted succinimide with fluorescent properties and remove moisture that causes hue deterioration in methacrylic resins. Therefore, it is preferable to obtain methacrylic resins and compositions thereof that have good hue even in light guides with long optical path lengths.

[0199] In the polymerization process, methacrylate monomers, any other monomers, polymerization initiators, polymerization solvents, chain transfer agents, etc., can be mixed in the N-substituted maleimide solution obtained from the above pretreatment process to prepare a monomer mixture, which can then be used in the polymerization.

[0200] (2) Reduction of unreacted N-substituted maleimide at the end of polymerization

[0201] The inventors have discovered that, although the detailed mechanism is unclear, if unreacted N-substituted maleimide is present at the end of the polymerization of methacrylic resins, a low molecular weight reaction byproduct containing N-substituted maleimide as its structural unit is generated in a heated devolatilization device or the like.

[0202] In order to control the content of fluorescent light-emitting substances in the methacrylic resin and the obtained resin-based light guide within the above-mentioned range, it is preferable that the total mass of unreacted N-substituted maleimide remaining after polymerization is 1000 ppm or less relative to 100% by mass of the polymerization solution at the end of polymerization, more preferably 10 ppm or more and 500 ppm or less by mass.

[0203] Furthermore, when N-aryl maleimides such as N-phenylmaleimide are used as N-substituted maleimides, the total mass of unreacted N-aryl maleimides remaining after polymerization is preferably 500 ppm or less, more preferably 10 ppm or more and 500 ppm or less, and even more preferably 10 ppm or more and 50 ppm or less, relative to 100 ppm of the polymerization solution at the end of polymerization.

[0204] Within these ranges, the content of fluorescent substances in the methacrylic resin and the resulting resin-based photoconductor can be controlled within the aforementioned range, which is therefore preferred. However, in order to set the amount of unreacted N-substituted maleimide to less than 10 ppm by mass, it is necessary to increase the polymerization temperature or increase the amount of polymerization initiator. Therefore, the amount of thermally modified maleimide and active free radicals will increase, leading to a deterioration in the color tone of the methacrylic resin, which is therefore not preferred.

[0205] As a means of controlling the amount of unreacted N-substituted maleimide within the aforementioned range after polymerization, a semi-batch polymerization method can be cited. In the semi-batch polymerization method, it is preferable to add 5 to 35% by mass of methacrylate monomer, based on 100% by mass of the total mass of all monomers supplied for polymerization (e.g., methacrylate, N-substituted maleimide, and any other monomers), 30 minutes after the start of polymerization. In other words, it is preferable to charge 65 to 95% by mass of the total mass of all monomers supplied for polymerization into the reactor before the addition of the polymerization initiator, and then add the remaining 5 to 35% by mass of methacrylate monomer 30 minutes after the start of polymerization initiator addition. The amount of methacrylate monomer added is more preferably 10 to 30% by mass, based on 100% by mass of the total mass of all monomers supplied for polymerization. When the amount of added methacrylate monomer is within the above range, the unreacted N-substituted maleimide reacts with the added methacrylate monomer, which can control the amount of unreacted N-substituted maleimide after polymerization within the above range, and is therefore preferred.

[0206] The start time and rate of addition of monomers can be appropriately selected based on the polymerization conversion rate. Furthermore, without hindering the effects of the invention or reducing the amount of unreacted N-substituted maleimide, a monomer mixture containing N-substituted maleimide monomers and other monomers can be added in addition to the methacrylate monomer.

[0207] By employing the semi-batch polymerization method described above, the amount of unreacted N-substituted maleimide monomers in the second half of the polymerization process can be reduced, minimizing the generation of fluorescent substances in the devolatilization process. This allows for the acquisition of methacrylic resins and compositions thereof that exhibit good hue even in light guides with long optical path lengths, and is therefore preferred.

[0208] The following is a detailed explanation of a method for manufacturing methacrylic resins having structural units derived from N-substituted maleimide monomers, specifically the case where the resin is manufactured by free radical polymerization in a semi-batch manner using solution polymerization.

[0209] In semi-batch polymerization, it is preferable to add 5-35% by mass of methacrylate monomer, based on 100% by mass of the total mass of all monomers supplied for polymerization (methacrylate, N-substituted maleimide, and any other monomers), 30 minutes after the start of polymerization initiation. In other words, it is preferable to add 65-95% by mass of the total 100% mass of monomers supplied for polymerization into the reactor before polymerization begins, and then add the remaining 5-35% by mass of methacrylate monomer 30 minutes after the start of polymerization initiation.

[0210] The amount of methacrylate monomer added is more preferably 10 to 30% by mass, based on 100% by mass of the total mass of all monomers supplied for polymerization.

[0211] The timing and rate of monomer addition can be appropriately selected based on the polymerization conversion rate.

[0212] In addition, without hindering the effects of the present invention or the improvement of the conversion rate of N-substituted maleimide monomers, a monomer mixture containing N-substituted maleimide monomers and other monomers may be added in addition to methacrylate monomers.

[0213] By employing the semi-batch polymerization method described above, the conversion rate of N-substituted maleimide monomers in the second half of the polymerization time can be increased, the content of fluorescent luminescent substances can be reduced, and a light guide with long optical path length, excellent light transmittance, easy control of the molecular weight distribution of the obtained polymer, and a resin and composition thereof with particularly suitable flowability for injection molding can be obtained, which is therefore preferred.

[0214] As for the polymerization solvent used, there are no particular restrictions as long as it is a solvent that appropriately maintains the viscosity of the reaction solution, with the aim of improving the solubility of the maleimide copolymer obtained by polymerization and preventing gelation.

[0215] As specific polymerization solvents, aromatic hydrocarbons such as toluene, xylene, ethylbenzene, and cumene can be used; ketones such as methyl isobutyl ketone, butyl cellosolve, methyl ethyl ketone, and cyclohexanone; and polar solvents such as dimethylformamide and 2-methylpyrrolidone can be used.

[0216] These can be used individually or in combination of two or more.

[0217] In addition, alcohols such as methanol, ethanol, and isopropanol can be used as polymerization solvents within a range that does not impede the solubility of the polymerization products during polymerization.

[0218] The amount of solvent used in polymerization is not particularly limited as long as it is an amount that allows polymerization to proceed, prevents the formation of copolymers and the precipitation of monomers during production, and can be easily removed. For example, when the total amount of the compounded monomers is set to 100% by mass, it is preferably set to 10 to 200% by mass. More preferably, it is 25 to 150% by mass, even more preferably 40 to 100% by mass, and even more preferably 50 to 100% by mass.

[0219] In this embodiment, it is also preferable to use a method in which the total amount of the monomers being polymerized is set to 100% by mass, the amount of solvent used in polymerization is in the range of 100% by mass or less, and polymerization is carried out while the solvent concentration is appropriately changed during polymerization.

[0220] More specifically, examples can be given of methods such as adding 40-60% by mass at the beginning of polymerization, adding the remaining 60-40% by mass during polymerization, and finally making the solvent amount less than 100% by mass when the total amount of monomers is set to 100% by mass.

[0221] This method can improve polymerization conversion rate, control molecular weight distribution, and produce resins and resin compositions with excellent injection molding properties, reduced content of fluorescent substances, and good color tone even when producing light guides with long optical path lengths. Therefore, it is preferred.

[0222] In solution polymerization, it is important to minimize the dissolved oxygen concentration in the polymerization solution; for example, the dissolved oxygen concentration is preferably below 10 ppm. The dissolved oxygen concentration can be measured, for example, using a dissolved oxygen meter (DO meter B-505, manufactured by Iijima Electronics Co., Ltd.). Methods for reducing the dissolved oxygen concentration include, appropriately, bubbling an inert gas into the polymerization solution, repeatedly pressurizing the container containing the polymerization solution with an inert gas to approximately 0.2 MPa and then releasing the pressure before polymerization, and introducing an inert gas into the container containing the polymerization solution.

[0223] As for the polymerization temperature, there are no particular limitations as long as the polymerization takes place at that temperature. Preferably, it is 70–180°C, more preferably 80–160°C, even more preferably 90–150°C, and even more preferably 100–150°C. From a productivity point of view, it is preferable to set it to 70°C or higher, and to suppress side reactions during polymerization and obtain polymers with the desired molecular weight and quality, it is preferable to set it to 180°C or lower.

[0224] Furthermore, regarding the polymerization time, there is no particular limitation as long as the required degree of polymerization can be obtained at the required conversion rate. From the viewpoint of productivity, etc., 2 to 15 hours is preferred, 3 to 12 hours is more preferred, and 4 to 10 hours is even more preferred.

[0225] As polymerization initiators, any initiator commonly used for free radical polymerization can be used, such as cumene hydroperoxide, dicumene hydroperoxide, di-tert-butyl peroxide, lauroyl peroxide, benzoyl peroxide, tert-butyl peroxyisopropyl carbonate, tert-amyl peroxy-2-ethylhexanoate, tert-amyl peroxyisononanoate, 1,1-di(tert-butyl peroxy)cyclohexane, and other organic peroxides; azo compounds such as 2,2'-azobis(isobutyronitrile), 1,1'-azobis(cyclohexaneformitrile), 2,2'-azobis(2,4-dimethylpentanonitrile), dimethyl-2,2'-azobisisobutyrate, etc.

[0226] These can be used individually or in combination of two or more.

[0227] The amount of polymerization initiator added can be 0.01 to 1% by mass, preferably 0.05 to 0.5% by mass, when the total amount of monomers used in the polymerization is set to 100% by mass.

[0228] There are no particular restrictions on the method of adding polymerization initiators, as long as the addition rate is not constant but varies according to the concentration of monomer remaining in the polymerization solution; it can be added continuously or intermittently. In the case of intermittent addition of the polymerization initiator, the amount added per unit time is not considered during the periods when no initiator is added.

[0229] In this embodiment, it is preferable to appropriately select the type and amount of polymerization initiator, as well as the polymerization temperature, so that the ratio of the total amount of free radicals generated by the polymerization initiator to the total amount of unreacted monomers remaining in the reaction system is always below a constant value.

[0230] By employing these methods, the generation of oligomers and low molecular weight substances in the later stages of polymerization can be suppressed, or overheating during polymerization can be suppressed to achieve polymerization stability.

[0231] During polymerization, chain transfer agents can be added as needed to carry out the polymerization reaction.

[0232] As chain transfer agents, chain transfer agents commonly used in free radical polymerization can be used, such as thiols like n-butylthiol, n-octylthiol, n-decylthiol, n-dodecylthiol, and 2-ethylhexyl mercaptoacetate; halogens like carbon tetrachloride, dichloromethane, and tribromomethane; and unsaturated hydrocarbons like α-methylstyrene dimer, α-terpinene, dipentene, and terpinene oil; etc.

[0233] These can be used individually or in combination of two or more.

[0234] These chain transfer agents can be added at any stage during the polymerization reaction without any particular limitation.

[0235] The amount of chain transfer agent added can be set to 0.01 to 1% by mass, preferably 0.05 to 0.5% by mass, when the total amount of monomers used in the polymerization is set to 100% by mass.

[0236] One method for recovering polymer from a polymer liquor obtained by solution polymerization is to separate the polymerization solvent and unreacted monomers through a process called devolatilization, thereby recovering the polymerization product. Here, devolatilization refers to the process of removing volatile components such as polymerization solvent, residual monomers, and reaction byproducts under heating and reduced pressure conditions.

[0237] In this embodiment, it is preferable to control the content of unreacted N-substituted maleimide monomers in the polymerization solution containing methacrylic resin supplied to the devolatilization process to below a specified concentration. Details are as described above in "(2) Reduction of unreacted N-substituted maleimide at the end of polymerization." In addition to the methods described above, for example, the following methods may be used: extending the polymerization time as much as possible to improve monomer conversion, or varying the addition rate of the polymerization initiator according to the concentration of unreacted monomers in the polymerization solution; performing polymerization while appropriately changing the solvent concentration; supplementing the polymerization with other monomers that are highly reactive with the remaining N-substituted maleimide monomers during the latter half of the polymerization period; or adding compounds such as α-terpinene that are highly reactive with N-substituted maleimide at the end of polymerization.

[0238] Residual amount of -N-substituted maleimide monomer-

[0239] As a method for determining the residual amount of N-substituted maleimide monomer in a polymerization solution containing a methacrylic resin, for example, a portion of the polymerization solution can be collected and weighed, the sample can be dissolved in chloroform to prepare a 5% by mass solution, n-decane can be added as an internal standard, and the concentration of residual N-substituted maleimide monomer in the sample can be determined using a gas chromatograph (Shimadzu Corporation, GC-2010), thereby determining the residual amount of N-substituted maleimide monomer. For more specific determination conditions, the conditions described in the examples below can be used.

[0240] (3) Methods to reduce shear devouring

[0241] As for the apparatus used in the above-mentioned devolatilization process, a devolatilization apparatus that mainly consists of a heat exchanger and a pressure reducing vessel and does not have a rotating part in its structure is preferred. By omitting the rotating part, shearing during devolatilization can be reduced, and resins with lower fluorescence luminescence can be obtained.

[0242] Specifically, a devolatilization device consisting of a devolatilization tank and a discharge device can be used. The devolatilization tank is configured with a heat exchanger at its upper part and a pressure reducing unit attached to a pressure reducing vessel of a size capable of devolatilization. The discharge device is a gear pump or the like for discharging the devolatilized polymer.

[0243] Regarding the aforementioned devolatilization apparatus, the polymerization solution is preheated by a heat exchanger, such as a multi-tube heat exchanger, a finned heat exchanger, or a flat-plate heat exchanger with a flat flow path and a heater, located at the top of a vacuum vessel. After preheating, the solution is fed into a devolatilization tank under heating and vacuum conditions to separate and remove the polymerization solvent, unreacted raw material mixture, polymerization byproducts, and other polymers. By using the devolatilization apparatus described above, which does not have a rotating section, it is possible to suppress low-molecular-weight, fluorescently emitting reaction byproducts originating from unreacted N-substituted maleimide. This allows for the control of the fluorescence intensity (content of fluorescently emitting substances) in the methacrylic resin and the resulting resin-based photoconductor within a specified range, which is therefore preferable. Furthermore, it is possible to obtain a methacrylic resin with a good hue, which is also preferable.

[0244] Examples of devices with rotating parts include the wiprene and exeva manufactured by Kobe Steel Environmental Solutions, Ltd., the KONTRO and tilting blade KONTRO manufactured by Hitachi, Ltd., and other thin-film evaporators; extruders with vent holes, etc.

[0245] In the devolatilization process of this embodiment, it is preferable to set the shear rate applied to the polymerization solution to 20 s. -1 Hereinafter, 10s is preferred.-1 The following is a further optimization with a time of 0.1s -1 More than 10s -1 The following method is used: The shearing rate is set to 0.1 s. -1 The above ensures that the flow of the molten resin is not too slow, thus suppressing color deterioration caused by increased residence time. Furthermore, setting it to 20 seconds... -1 The following method can inhibit the formation of fluorescent byproducts caused by shearing.

[0246] Here, for example, the shear rate γ in the extruder is calculated by the following formula.

[0247] γ=(π×D×N) / H

[0248] (In the formula, D represents the screw diameter (m), N represents the screw rotation speed per second, and H represents the screw groove depth (m).)

[0249] In addition, in the case of a flat flow path, the shear rate γ is calculated by the following formula.

[0250] γ=(6×Q) / (w×h 2 )

[0251] (In the formula, Q represents the volumetric flow rate (m³) through the flat plate flow path.) 3 / s), where w represents the width (m) of the flat flow path, and h represents the distance (m) between the flat plates.

[0252] In this embodiment, a flat-plate heat exchanger having a flat-plate flow path and a heater is preferably used as the heat exchanger disposed on the upper part of the pressure reducing vessel. More preferably, a flat-plate heat exchanger having a flat-plate flow path and a heater, wherein the flat-plate flow path has a stacked structure, and the stacked structure has a plurality of slit-shaped flow paths with a rectangular cross-section on the same plane.

[0253] The polymerization solution supplied to the devolatilization unit is heated from the central part of the heat exchanger into the slit-shaped flow path. The heated polymerization solution is then supplied from the slit-shaped flow path into a depressurized vessel integrated with the heat exchanger, where it is flash evaporated.

[0254] This type of devouring method is sometimes called rapid devouring, and in this invention, it will also be referred to as rapid devouring.

[0255] Alternatively, two or more of the above-mentioned devolatilization devices can be connected in series to perform devolatilization in two or more stages.

[0256] The temperature range for heating using a heat exchanger with an attached devolatilization device can be set to 100°C or higher and 300°C or lower, preferably 100°C to 160°C above the glass transition temperature (Tg) of the methacrylic resin, and more preferably 110°C to 150°C above Tg. The temperature range for the devolatilization tank, which is heated and maintained at this temperature, can also be set to 100°C or higher and 300°C or lower, preferably 100°C to 160°C above Tg, and more preferably 110°C to 150°C above Tg. When the temperatures of the heat exchanger and the devolatilization tank are within this range, the thermal modification of residual 2-amino-N-substituted succinimidyl ether can be suppressed, and the formation of fluorescent substances can be suppressed, thus this is preferable. Furthermore, it effectively prevents the increase of residual volatile components, improving the thermal stability and product quality of the obtained methacrylic resin, thus this is preferable.

[0257] The vacuum level inside the devolatilization tank can be set in the range of 5 to 300 Torr, preferably in the range of 10 to 200 Torr. When the vacuum level is below 300 Torr, unreacted monomers or mixtures of unreacted monomers and polymerization solvents can be effectively separated and removed without reducing the thermal stability and quality of the obtained thermoplastic copolymer. When the vacuum level is above 5 Torr, industrial implementation is easier.

[0258] The average residence time in the devolatilization tank can be 5 to 60 minutes, preferably 5 to 45 minutes. When the average residence time is within this range, devolatilization can be effectively carried out while suppressing coloring and decomposition caused by the thermal modification of the polymer, which is therefore preferred.

[0259] The polymer recovered through the devolatilization process is then processed into granules using a process called granulation.

[0260] In the granulation process, molten resin is extruded in a linear fashion using at least one transport granulation device selected from gear pumps with porous molds as auxiliary equipment, single-shaft extruders, and bi-shaft extruders. The granules are then processed using cold cutting, air hot cutting, underwater wire bundle cutting, or underwater cutting methods. From the viewpoint of controlling the generation of fluorescent byproducts caused by shearing, a transport device with a low shear rate is preferred over an extruder.

[0261] In this embodiment, in order to obtain a highly controlled resin composition, it is preferable to use a granulation method that minimizes the contact between the resin composition, which is in a molten state at high temperature, and allows for rapid cooling and solidification.

[0262] In this case, it is preferable to reduce the temperature of the molten resin to the extent possible, and to minimize the residence time from the outlet of the porous mold to the surface of the cooling water, while also using a higher temperature of the cooling water as possible, and to granulate under feasible conditions.

[0263] For example, the melting resin temperature is preferably 220 to 280°C, more preferably 230 to 270°C, the residence time from the porous mold outlet to the cooling water surface is preferably less than 5 seconds, more preferably less than 3 seconds, and the cooling water temperature is preferably in the range of 30 to 80°C, more preferably 40 to 60°C.

[0264] By implementing the process within these ranges of molten resin temperature and cooling water temperature, it is possible to obtain methacrylic resins and their compositions with less coloring and lower moisture content, which is therefore preferred.

[0265] From the viewpoint of thermal stability and product quality, it is preferable to have a lower content of residual monomers in the methacrylate resin after the devolatilization process. Specifically, the content of methacrylate monomers is preferably 3000 ppm by mass or less, more preferably 2000 ppm by mass or less. The content of N-substituted maleimide monomers is preferably 200 ppm by mass or less, more preferably 100 ppm by mass or less, in total.

[0266] In addition, the content of residual polymerization solvent is preferably 500 ppm by mass or less, more preferably 300 ppm by mass or less.

[0267] - Method for manufacturing methacrylic resins containing glutarimide structural units-

[0268] Methods for manufacturing methacrylic resins having glutarimide structural units on the main chain include any one of bulk polymerization, solution polymerization, suspension polymerization, precipitation polymerization, and emulsion polymerization, with suspension polymerization, bulk polymerization, and solution polymerization being preferred, and solution polymerization being even more preferred.

[0269] In the manufacturing method of this embodiment, as a polymerization method, for example, any one of batch polymerization, semi-batch polymerization, or continuous polymerization can be used.

[0270] In the manufacturing method of this embodiment, a method of polymerizing monomers by free radical polymerization is preferred.

[0271] A methacrylic resin having glutarimide structural units on its main chain, such as those described in Japanese Patent Application Publication No. 2006-249202, Japanese Patent Application Publication No. 2007-009182, Japanese Patent Application Publication No. 2007-009191, Japanese Patent Application Publication No. 2011-186482, and International Publication No. 2012 / 114718, can be formed by the methods described in those publications.

[0272] The following is a detailed description of an example of a method for manufacturing methacrylic resins having glutarimide structural units, in which solution polymerization is used to manufacture the resin via batch free radical polymerization.

[0273] First, a (meth)acrylate polymer is produced by polymerizing (meth)acrylates such as methyl methacrylate. In the case where an aromatic vinyl unit is included in a methacrylate resin having glutarimide structural units, a (meth)acrylate-aromatic vinyl copolymer is produced by copolymerizing the (meth)acrylate and an aromatic vinyl unit (e.g., styrene).

[0274] Examples of solvents used in polymerization include aromatic hydrocarbons such as toluene, xylene, and ethylbenzene; ketones such as methyl ethyl ketone and methyl isobutyl ketone; and so on.

[0275] These solvents can be used individually or in combination of two or more.

[0276] The amount of solvent used in polymerization is not particularly limited as long as it is an amount that allows polymerization to proceed, does not cause precipitation of copolymers or monomers during production, and can be easily removed. For example, when the total amount of the compounded monomers is set to 100% by mass, it is preferably 10 to 200% by mass. More preferably, it is 25 to 200% by mass, even more preferably 50 to 200% by mass, and even more preferably 50 to 150% by mass.

[0277] As for the polymerization temperature, there are no particular limitations as long as the polymerization takes place at any temperature, but 50–200°C is preferred, more preferably 80–200°C. Further preferred is 90–150°C, even more preferably 100–140°C, and still more preferably 100–130°C. From a productivity point of view, a temperature of 70°C or higher is preferred, and to suppress side reactions during polymerization and obtain a polymer with the desired molecular weight and quality, a temperature of 180°C or lower is preferred.

[0278] As for the polymerization time, it is not particularly limited as long as the desired conversion rate is met, but from the viewpoint of productivity, it is preferred to be 0.5 to 15 hours, more preferably 2 to 12 hours, and even more preferably 4 to 10 hours.

[0279] During polymerization, polymerization initiators and chain transfer agents can be added as needed.

[0280] There are no particular limitations on the polymerization initiator; for example, polymerization initiators disclosed in the preparation method of methacrylic resin having structural units derived from the above-mentioned N-substituted maleimide monomers can be used.

[0281] These polymerization initiators can be used alone or in combination of two or more.

[0282] These polymerization initiators can be added at any stage as long as the polymerization reaction is in progress.

[0283] The amount of polymerization initiator added can be set appropriately according to the combination of monomers and reaction conditions, and there is no particular limitation. When the total amount of monomers used in polymerization is set to 100% by mass, it can be set to 0.01 to 1% by mass, preferably 0.05 to 0.5% by mass.

[0284] As a chain transfer agent, chain transfer agents used in conventional free radical polymerization can be used, such as those disclosed in the preparation method of methacrylic resins having structural units derived from the above-described N-substituted maleimide monomers.

[0285] These can be used individually or in combination of two or more.

[0286] These chain transfer agents can be added at any stage of the polymerization reaction, without any particular limitation.

[0287] Regarding the amount of chain transfer agent added, there is no particular limitation as long as it is within the range that allows the desired degree of polymerization to be obtained under the polymerization conditions used. Preferably, it can be set to 0.01 to 1% by mass, and more preferably 0.05 to 0.5% by mass, when the total amount of monomer used in the polymerization is set to 100% by mass.

[0288] The appropriate method for adding polymerization initiators and chain transfer agents in the polymerization process can be, for example, the method described in the preparation method of a methacrylic resin having structural units derived from the above-described N-substituted maleimide monomer.

[0289] The dissolved oxygen concentration in the polymerization solution may, for example, be a value disclosed in a method for preparing a methacrylic resin having structural units derived from the aforementioned N-substituted maleimide monomer.

[0290] Next, an imidization reaction (imidization step) is carried out by reacting the above-mentioned (meth)acrylate polymer or the above-mentioned methacrylate-aromatic vinyl copolymer with an imidizing agent. This allows the manufacture of methacrylate resins having glutarimide structural units.

[0291] There are no particular limitations on the imidizing agent mentioned above; any imidizing agent that can generate a glutarimide structural unit represented by the above general formula (3) is acceptable.

[0292] Specifically, ammonia or a primary amine can be used as an imidizing agent. Examples of primary amines include methylamine, ethylamine, n-propylamine, isopropylamine, n-butylamine, isobutylamine, tert-butylamine, n-hexylamine, etc., which contain aliphatic hydrocarbon groups; cyclohexylamine, etc., which contain alicyclic hydrocarbon groups; etc.

[0293] Among the above imidizing agents, ammonia, methylamine, and cyclohexylamine are preferred from the perspectives of cost and physical properties, with methylamine being particularly preferred.

[0294] In this imidization process, by adjusting the addition ratio of the imidizing agent, the content of glutarimide structural units in the obtained methacrylic resin having glutarimide structural units can be adjusted.

[0295] There are no particular limitations on the method for carrying out the above imidization reaction. Conventionally known methods can be used, for example, imidization reaction can be carried out by using an extruder or a batch reaction tank.

[0296] There are no particular limitations on the extruders mentioned above; for example, single-spindle extruders, twin-spindle extruders, multi-spindle extruders, etc., can be used.

[0297] A biaxial extruder is preferred. A biaxial extruder facilitates the mixing of the raw polymer and the imidizing agent.

[0298] Examples of biaxial extruders include non-meshing co-rotating type, meshing co-rotating type, non-meshing counter-rotating type, and meshing counter-rotating type.

[0299] The extruders illustrated above can be used individually or in series in multiple units.

[0300] In addition, the extruder is equipped with a vent that can reduce the pressure to below atmospheric pressure, which can remove byproducts or monomers such as imidizing agents and methanol from the reaction, making it particularly preferred.

[0301] In manufacturing methacrylic resins having glutarimide-based structural units, in addition to the imidization step described above, an esterification step may be included to treat the carboxyl groups of the resin using an esterifying agent such as dimethyl carbonate. In this case, catalysts such as trimethylamine, triethylamine, and tributylamine may be used in combination for treatment.

[0302] Similar to the imidization process described above, the esterification process can be performed, for example, by using an extruder or a batch reaction tank.

[0303] In addition, for the purpose of removing excess esterifying agents, methanol, and other byproducts or monomers, it is preferable to install a vent on the device that can reduce the pressure to below atmospheric pressure.

[0304] Methacrylic resins that have undergone imidization and esterification processes as needed are melted and extruded in a wire-like manner from an extruder with a multi-hole die, and processed into granules using methods such as cold cutting, air hot cutting, underwater wire harness cutting, and underwater cutting.

[0305] In addition, to reduce the amount of foreign matter in the resin, it is preferable to use a method that involves dissolving the methacrylic resin in organic solvents such as toluene, methyl ethyl ketone, and dichloromethane, filtering the obtained methacrylic resin solution, and then volatilizing the organic solvent.

[0306] From the viewpoint of reducing fluorescence intensity (the content of fluorescent luminescent substances), it is preferable to imidize the polymerization solution after polymerization in a batch reaction tank and not to use a biaxial extruder that is subject to shear forces.

[0307] The imidization reaction is preferably carried out at 130–250°C, more preferably at 150–230°C, and even more preferably at 170–190°C. Furthermore, the reaction time is preferably 10 minutes to 5 hours, more preferably 30 minutes to 2 hours.

[0308] From the viewpoint of reducing fluorescence intensity, it is preferable to perform devolatilization by the (3) shear-reducing devolatilization method described in the preparation method of methacrylic resin having structural units derived from the above-mentioned N-substituted maleimide monomer after the imidization step, and then granulate.

[0309] - Method for manufacturing methacrylic resins containing lactone ring structural units -

[0310] As a method for manufacturing methacrylic resins having lactone ring structural units on the main chain, a method can be used to form lactone ring structures by cyclization reaction after polymerization. Preferably, the monomer is polymerized by solution polymerization using a solvent, based on promoting the cyclization reaction, by free radical polymerization.

[0311] In the manufacturing method of this embodiment, as a polymerization method, for example, any one of batch polymerization, semi-batch polymerization, or continuous polymerization can be used.

[0312] Methacrylic acid resins having lactone ring structural units on the main chain can be formed, for example, by the methods described in Japanese Patent Application Publication Nos. 2001-151814, 2004-168882, 2005-146084, 2006-96960, 2006-171464, 2007-63541, 2007-297620, and 2010-180305.

[0313] The following is a specific example of a method for manufacturing methacrylic resins having lactone ring structural units, specifically illustrating the case where the resin is manufactured by free radical polymerization in an intermittent manner using solution polymerization.

[0314] As a method for manufacturing methacrylic resins having lactone ring structural units, a method can be used to form lactone ring structures by cyclization reaction after polymerization, preferably solution polymerization using a solvent to promote cyclization reaction.

[0315] Examples of solvents used in polymerization include aromatic hydrocarbons such as toluene, xylene, and ethylbenzene; ketones such as methyl ethyl ketone and methyl isobutyl ketone; and so on.

[0316] These solvents can be used individually or in combination of two or more.

[0317] As for the amount of solvent during polymerization, there are no particular limitations as long as the conditions for polymerization to proceed and gelation to be suppressed. For example, when the total amount of the complexed monomers is set to 100% by mass, it is preferable to set it to 50 to 200% by mass, and more preferably 100 to 200% by mass.

[0318] To effectively suppress gelation of the polymerization solution and promote the cyclization reaction after polymerization, polymerization is preferably carried out in a manner where the concentration of the polymer generated in the reaction mixture after polymerization is 50% by mass or less. Furthermore, it is preferable to appropriately add a polymerization solvent to the reaction mixture and control the concentration to be 50% by mass or less as described above.

[0319] There are no particular limitations on the method of appropriately adding the polymerization solvent to the reaction mixture; for example, the polymerization solvent can be added continuously or intermittently.

[0320] The added polymerization solvent can be a single solvent or a mixture of two or more solvents.

[0321] There are no particular limitations on the polymerization temperature, as long as it is the temperature at which polymerization takes place. From the viewpoint of productivity, 50 to 200°C is preferred, and 80 to 180°C is more preferred.

[0322] As for the aggregation time, it is not particularly limited as long as the desired conversion rate is met. From the viewpoint of productivity, it is preferred to be 0.5 to 10 hours, and more preferably 1 to 8 hours.

[0323] During polymerization, polymerization initiators and chain transfer agents can be added as needed.

[0324] There are no particular limitations on the polymerization initiator; for example, polymerization initiators disclosed in the preparation method of methacrylic resin having structural units derived from the above-mentioned N-substituted maleimide monomers can be used.

[0325] These polymerization initiators can be used alone or in combination of two or more.

[0326] These polymerization initiators can be added at any stage as long as the polymerization reaction is in progress.

[0327] The amount of polymerization initiator added can be set appropriately according to the combination of monomers, reaction conditions, etc., and there is no particular limitation. When the total amount of monomers used in polymerization is set to 100% by mass, it can be set to 0.05 to 1% by mass.

[0328] As a chain transfer agent, chain transfer agents used in conventional free radical polymerization can be used, such as those disclosed in the preparation method of methacrylic resins having structural units derived from the above-described N-substituted maleimide monomers.

[0329] These can be used individually or in combination of two or more.

[0330] These chain transfer agents can be added at any stage during the polymerization reaction, without any particular limitation.

[0331] The amount of chain transfer agent added is not particularly limited as long as it is within the range that allows the desired degree of polymerization to be obtained under the polymerization conditions used. Preferably, it can be set to 0.05 to 1% by mass when the total amount of monomer used in the polymerization is set to 100% by mass.

[0332] The appropriate method for adding polymerization initiators and chain transfer agents in the polymerization process may be, for example, the method described in the preparation method of methacrylic resin having structural units derived from the above-mentioned N-substituted maleimide monomers.

[0333] The dissolved oxygen concentration in the polymerization solution may, for example, be a value disclosed in a method for preparing a methacrylic resin having structural units derived from the aforementioned N-substituted maleimide monomer.

[0334] The methacrylic acid resin with lactone ring structural units in this embodiment can be obtained by cyclization reaction after the above polymerization reaction is completed. Therefore, it is preferable to supply the lactone cyclization reaction in a solvent-containing state without removing the polymerization solvent from the polymerization reaction solution.

[0335] The copolymer obtained by polymerization is subjected to heat treatment to induce a cyclization condensation reaction between the hydroxyl (hydroxyl) groups and ester groups present in the molecular chain of the copolymer, thereby forming an lactone ring structure.

[0336] During the heat treatment to form the lactone ring structure, reaction equipment equipped with a vacuum device or a devolatilization device for removing alcohols that may be produced as byproducts of cyclization condensation, or an extruder equipped with a devolatilization device, can also be used.

[0337] In order to promote the cyclization condensation reaction during the formation of the lactone ring structure, a cyclization condensation catalyst can be used for heating treatment as needed.

[0338] Specific examples of cyclization condensation catalysts include, for instance, monoalkyl, dialkyl, or trialkyl esters, dialkyl, or trialkyl esters, such as methyl phosphite, ethyl phosphite, phenyl phosphite, dimethyl phosphite, diethyl phosphite, diphenyl phosphite, trimethyl phosphite, and triethyl phosphite; monoalkyl, dialkyl, or trialkyl esters, such as methyl phosphate, ethyl phosphate, 2-ethylhexyl phosphate, octyl phosphate, isodecanyl phosphate, lauryl phosphate, stearyl phosphate, isostearyl phosphate, dimethyl phosphate, diethyl phosphate, di-2-ethylhexyl phosphate, diisodecyl phosphate, dilauryl phosphate, disostearyl phosphate, diisostearyl phosphate, trimethyl phosphate, triethyl phosphate, triisodecyl phosphate, trilauryl phosphate, tristearyl phosphate, and triisostearyl phosphate; organozinc compounds such as zinc acetate, zinc propionate, and octyl zinc; etc.

[0339] These can be used individually or in combination of two or more.

[0340] The amount of cyclization condensation catalyst used is not particularly limited, but for example, it is preferably 0.01 to 3% by mass, more preferably 0.05 to 1% by mass, relative to 100% by mass of the methacrylic resin.

[0341] When the amount of catalyst used is 0.01% by mass or more, the reaction rate of the cyclization condensation reaction is effectively improved. When the amount of catalyst used is 3% by mass or less, the coloring of the obtained polymer and the cross-linking of the polymer are effectively prevented, making it difficult to melt-form.

[0342] There is no particular limitation on the timing of addition of the catalyst for cyclization condensation. For example, it can be added at the beginning of the cyclization condensation reaction, during the reaction, or at both of these stages.

[0343] When cyclization condensation reactions occur in the presence of a solvent, devolatilization can also occur simultaneously.

[0344] Regarding the apparatus used in the case of simultaneously performing cyclization condensation reaction and devolatilization process, there are no particular limitations. It can be a devolatilization device consisting of a heat exchanger and a devolatilization tank, an extruder with vent holes, and preferably an apparatus in series with the devolatilization device and the extruder. More preferably, it is a biaxial extruder with vent holes.

[0345] As a biaxial extruder with vent holes, an extruder with vent holes having a plurality of vent orifices is preferred.

[0346] When using an extruder with vents, the reaction processing temperature is preferably 150–350°C, more preferably 200–300°C. When the reaction processing temperature is below 150°C, the cyclization condensation reaction becomes incomplete, resulting in more residual volatile components. Conversely, when the reaction processing temperature is above 350°C, it can cause discoloration and decomposition of the obtained polymer.

[0347] When using an extruder with vents, the vacuum level is preferably 10 to 500 Torr, more preferably 10 to 300 Torr. When the vacuum level is greater than 500 Torr, volatile components may sometimes remain. Conversely, when the vacuum level is less than 10 Torr, industrial implementation may sometimes become difficult.

[0348] In carrying out the above-mentioned cyclization condensation reaction, it is also preferable to add alkaline earth metal and / or amphoteric metal salts of organic acids during granulation to deactivate the residual cyclization condensation catalyst.

[0349] Alkaline earth metal and / or amphoteric metal salts that act as organic acids, for example, calcium acetoacetate, calcium stearate, zinc acetate, zinc octanoate, zinc 2-ethylhexanoate, etc., can be used.

[0350] After undergoing the cyclization and condensation reaction process, the methacrylic resin is melted and extruded in strands from an extruder with a porous die, and then processed into granules using cold cutting, air hot cutting, underwater wire harness cutting, and underwater cutting methods.

[0351] It should be noted that the lactone formation described above for forming lactone ring structural units can be carried out either after the resin is manufactured and before the resin composition is manufactured (described later), or it can be carried out during the manufacture of the resin composition, together with the melt blending of the resin and other components.

[0352] From the viewpoint of reducing fluorescence intensity (content of fluorescent luminescent material), it is preferable to cyclize the lactone in a batch reaction tank after polymerization without using a biaxial extruder subjected to shear force. From the viewpoint of reducing fluorescence intensity, it is preferable to perform devolatilization using the shear-reducing devolatilization method (3) described in the method for preparing methacrylic resins having structural units derived from the above-mentioned N-substituted maleimide monomers after the lactone cyclization step, followed by granulation.

[0353] [additive]

[0354] The resin composition constituting the light guide of the head-mounted display in this embodiment may contain various additives, within the range described above that does not significantly impair the effects of the present invention.

[0355] As additives, there are no particular limitations. Examples include antioxidants, hindered amine light stabilizers, UV absorbers, mold release agents, other thermoplastic resins, alkane-based processing oils, cycloalkane-based processing oils, aromatic processing oils, alkanes, organopolysiloxanes, mineral oils, etc., softeners / plasticizers, flame retardants, antistatic agents, organic fibers, iron oxides, etc., inorganic fillers such as pigments, glass fibers, carbon fibers, metal whiskers, etc., reinforcing agents, colorants; phosphites, phosphonites, phosphates, etc., organophosphorus compounds, other additives, or mixtures thereof.

[0356] -Antioxidants-

[0357] The resin composition constituting the light guide of the head-mounted display in this embodiment preferably contains an antioxidant that inhibits deterioration and discoloration during molding or use.

[0358] Examples of antioxidants mentioned above include hindered phenolic antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants, but they are not limited to these antioxidants.

[0359] These antioxidants can be used in one or in combination of two or more.

[0360] Furthermore, from the viewpoint of improving thermal stability and suppressing molding defects, it is preferable to use a plurality of heat stabilizers, for example, it is preferable to use at least one selected from phosphorus-based antioxidants and sulfur-based antioxidants and hindered phenolic antioxidants.

[0361] Examples of hindered phenolic antioxidants include pentaerythritol tetra[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], thiodiethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 3,3',3”,5,5',5”-hexa-tert-butyl-a,a',a”-(trimethylbenzene-2,4,6-triyl)tri-p-cresol, 4,6-bis(octylthiomethyl)-o-cresol, 4,6-bis(dodecylthiomethyl)-o-cresol, ethylenebis(oxyethylene)bis[3-(5-tert-butyl-4-hydroxym-tolyl)propionate], and hexamethylenebis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]. [Acid esters], 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,3,5-tris[(4-tert-butyl-3-hydroxy-2,6-dimethylyl)methyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazine-2-ylamino)phenol, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, 2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl acrylate, etc., but not limited to these hindered phenolic antioxidants.

[0362] Particularly preferred are pentaerythritol tetra[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl ester.

[0363] In addition, hindered phenolic antioxidants, as the aforementioned antioxidants, can be commercially available phenolic antioxidants. Examples of such commercially available phenolic antioxidants include Irganox 1010 (Irganox 1010: pentaerythritol tetratetra[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, manufactured by BASF), Irganox 1076 (Irganox 1076: octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, manufactured by BASF), Irganox 1330 (Irganox 1330: 3,3',3”,5,5',5”-hexa-tert-butyl-a,a',a”-(trimethylbenzene-2,4,6-triyl)tri-p-cresol, manufactured by BASF), and Irganox... 3114 (Irganox 3114: 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, manufactured by BASF), Irganox 3125 (Irganox 3125, manufactured by BASF), ADK STAB AO-60 (Adekastab AO-60) (pentaerythritol tetratetra[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], manufactured by ADEKA), ADK STAB AO-80 (Adekastab AO-80)(3,9-bis{2-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxellaspiro[5.5]undecane, manufactured by ADEKA), Sumilizer BHT (Sumitomo Chemical), Cyanox 1790 (Sitech), Sumilizer GA-80 (Sumitomo Chemical), Sumilizer GS (Sumitomo Chemical Co., Ltd.): 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl acrylate]-4,6-di-tert-pentylphenyl acrylate, manufactured by Sumitomo Chemical Co., Ltd., etc., but not limited to these.

[0364] Among these commercially available phenolic antioxidants, from the viewpoint of imparting thermal stability to the resin, Irganox 1010, ADK STAB AO-60, ADK STAB AO-80, Irganox 1076, and Sumilizer GS are preferred.

[0365] These can be used individually or in combination with two or more.

[0366] In addition, examples of phosphorus-based antioxidants that can be used as the aforementioned antioxidants include tris(2,4-di-tert-butylphenyl) phosphite, bis(2,4-bis(1,1-dimethylethyl)-6-methylphenyl) ethyl phosphite, tetra(2,4-di-tert-butylphenyl)(1,1-biphenyl)-4,4'-diyl diphosphite, bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite, and bis(2,6-di-tert-butyl-4-methylphenyl) quaternary ammonium chloride. Pentylenetetroxide diphosphite, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, tetra(2,4-tert-butylphenyl)(1,1-biphenyl)-4,4'-diyldiphosphite, di-tert-butyl-m-tolylphosphite, 4-[3-[(2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphinecycloheptyl)-6-yloxy]propyl]-2-methyl-6-tert-butylphenol, etc., but not limited to these.

[0367] In addition, commercially available phosphorus-based antioxidants can be used as phosphorus-based antioxidants. Examples of such commercially available phosphorus-based antioxidants include Irgafos 168 (tris(2,4-di-tert-butylphenyl)phosphite, manufactured by BASF), Irgafos 12 (tris[2-[[2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxophosphazene-hepta-6-yl]oxy]ethyl]amine, manufactured by BASF), Irgafos 38 (bis(2,4-bis(1,1-dimethylethyl)-6-methylphenyl)ethyl phosphite, manufactured by BASF), and ADK. STAB-229K (ADEKA STAB 329K, manufactured by ADEKA), ADK STAB PEP-36 (ADEKA STAB PEP-36, manufactured by ADEKA), ADK STAB PEP-36A (ADEKA STAB PEP-36A, manufactured by ADEKA), ADK STAB PEP-8 (ADEKA STAB PEP-8, manufactured by ADEKA), ADKSTAB HP-10 (ADEKA STAB HP-10, manufactured by ADEKA), ADK STAB 2112 (ADEKA STAB 2112, manufactured by ADEKA), ADK STAB 1178 (ADEKA STAB 1178, manufactured by ADEKA), ADK STAB 1500 (アデカスタブ1500, made by ADEKA), Sandstab P-EPQ (made by CLARIANT, クラリアント), Weston 618 (ウェストン618, made by GE), Weston 619G (ウェストン619G, made by GE), Ultranox 626 (ウルトラノックス626, made by GE), Sumilizer GP (Sumitomo Chemical Co., Ltd.): 4-[3-[(2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxanecycloheptyl)-6-yloxy]propyl]-2-methyl-6-tert-butylphenol, manufactured by Sumitomo Chemical Co., Ltd.), HCA (9,10-dihydro-9-oxa-10-phosphenanthrene-10-oxide, manufactured by Sanko Co., Ltd.), etc., but not limited to these.

[0368] Among these commercially available phosphorus-based antioxidants, from the viewpoint of imparting thermal stability to the resin and their combined effect with various antioxidants, Irgafos 168, ADK STAB PEP-36, ADK STAB PEP-36A, ADK STAB HP-10, and ADK STAB1178 are preferred, with ADK STAB PEP-36A and ADK STAB PEP-36 being particularly preferred.

[0369] These phosphorus-based antioxidants can be used alone or in combination of two or more.

[0370] In addition, examples of sulfur-based antioxidants used as the aforementioned antioxidants include 2,4-bis(dodecylthiomethyl)-6-methylphenol (Irganox 1726, manufactured by BASF), 2,4-bis(octylthiomethyl)-6-methylphenol (Irganox 1520L, manufactured by BASF), and 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-dodecylthio]propionate] (ADKSTAB) AO-412S (ADEKA Corporation), 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-dodecylthio]propionate (KEMINOXPLS, CHEMIPRO Chemical Co., Ltd.), di(tridecyl)3,3'-thiodipropionate (AO-503, ADEKA Corporation), etc., but not limited to these.

[0371] Among these commercially available sulfur antioxidants, ADK STAB AO-412S and KEMINOX PLS are preferred from the viewpoints of imparting thermal stability to the resin, the synergistic effect with various antioxidants, and processability.

[0372] These sulfur-based antioxidants can be used alone or in combination of two or more.

[0373] The content of antioxidant is only required to achieve the effect of improving thermal stability. If the content is excessive, problems such as exudation may occur during processing. Therefore, relative to 100% by mass of methacrylic resin, it is preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 1% by mass or less, even more preferably 0.8% by mass or less, even more preferably 0.01 to 0.8% by mass, and particularly preferably 0.01 to 0.5% by mass.

[0374] There are no particular limitations on the timing of adding antioxidants. Examples include: adding them to the monomer solution before polymerization begins; adding them to the polymer solution after polymerization and mixing them before supplying them to the devolatilization process; adding them to the molten polymer after devolatilization and mixing them before granulation; and adding and mixing them during the melt extrusion of the devolatilized and granulated granules. Among these, from the viewpoint of preventing thermal degradation and discoloration during the devolatilization process, it is preferable to add the antioxidant to the polymer solution after polymerization and mixing it before the devolatilization process, and then supply it to the devolatilization process.

[0375] -Hindered amine light stabilizers-

[0376] The resin composition constituting the light guide of the head-mounted display in this embodiment may contain a hindered amine light stabilizer.

[0377] Hindered amine light stabilizers are not particularly limited, but are preferably compounds containing three or more ring structures. Here, the ring structure is preferably selected from at least one of the group consisting of aromatic rings, aliphatic rings, aromatic heterocycles, and non-aromatic heterocycles. When a compound has two or more ring structures, these ring structures may be the same as or different from each other.

[0378] As hindered amine light stabilizers, examples include, specifically, bis(1,2,2,6,6-pentamethyl-4-piperidinyl)[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butyl malonate, mixtures of bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate and methyl 1,2,2,6,6-pentamethyl-4-piperidinyl sebacate, bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, and N,N'-bis... (2,2,6,6-Tetramethyl-4-piperidinyl)-N,N'-dicarboxyhexamethylenediamine, dibutylamine·1,3,5-triazine·N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexamethylenediamine and N-(2,2,6,6-tetramethyl-4-piperidinyl)butylamine condensate, poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidinyl)butylamine] [(2,2,6,6-tetramethyl-4-piperidinyl)imino}, tetra(1,2,2,6,6-pentamethyl-4-piperidinyl)butane-1,2,3,4-tetracarboxylic acid ester, tetra(2,2,6,6-tetramethyl-4-piperidinyl)butane-1,2,3,4-tetracarboxylic acid ester, 1,2,2,6,6-pentamethyl-4-piperidinol and β,β,β',β'-tetramethyl-2,4,8,10-tetraoxazolo[5.5]undecane-3, The reaction products of 9-diethanol, the reaction products of 2,2,6,6-tetramethyl-4-piperidinol with β,β,β',β'-tetramethyl-2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diethanol, bis(1-undecoxy-2,2,6,6-tetramethylpiperidin-4-yl) carbonate, 1,2,2,6,6-pentamethyl-4-piperidinyl methacrylate, 2,2,6,6-tetramethyl-4-piperidinyl methacrylate, etc., but not limited to these.

[0379] Preferably, the polymers contain three or more ring structures, such as bis(1,2,2,6,6-pentamethyl-4-piperidinyl)[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butyl malonate, condensates of dibutylamine·1,3,5-triazine·N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,6-hexamethylenediamine and N-(2,2,6,6-tetramethyl-4-piperidinyl)butylamine, or poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-dimethyl] The reaction products of 1,2,2,6,6-tetramethyl-4-piperidinyl)imino}{(2,2,6,6-tetramethyl-4-piperidinyl)imino}, 1,2,2,6,6-pentamethyl-4-piperidinol with β,β,β',β'-tetramethyl-2,4,8,10-tetraoxellaspiro[5.5]undecane-3,9-diethanol, and 2,2,6,6-tetramethyl-4-piperidinol with β,β,β',β'-tetramethyl-2,4,8,10-tetraoxellaspiro[5.5]undecane-3,9-diethanol.

[0380] The content of the hindered amine light stabilizer should be sufficient to achieve the effect of improving light stability. In case of excessive content, problems such as exudation may occur during processing. Therefore, relative to 100% by mass of the methacrylic resin, it is preferably 5% by mass or less, more preferably 3% by mass or less, even more preferably 1% by mass or less, even more preferably 0.8% by mass or less, even more preferably 0.01 to 0.8% by mass, and particularly preferably 0.01 to 0.5% by mass.

[0381] --UV absorber--

[0382] The resin composition constituting the light guide of the head-mounted display in this embodiment may contain an ultraviolet absorber.

[0383] There are no particular limitations on the ultraviolet absorber, but it is preferred to be an ultraviolet absorber with its maximum absorption wavelength in the range of 280 to 380 nm. Examples include benzotriazole compounds, benzotriazine compounds, benzophenone compounds, oxobenzophenone compounds, benzoic acid ester compounds, phenolic compounds, oxazole compounds, cyanoacrylate compounds, and benzoxazinone compounds.

[0384] Examples of benzotriazole compounds include 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazole-2-yl)phenol], 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole, 2-(2H-benzotriazole-2-yl)-p-cresol, 2-(2H-benzotriazole-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol, 2-benzotriazole-2-yl-4,6-di-tert-butylphenol, 2-[5-chloro(2H)-benzotriazole-2-yl]-4-methyl-6-tert-butylphenol, 2-(2H-benzotriazole-2-yl)-4,6-di-tert-butylphenol, and 2-(2H-benzotriazole-2-yl)-4-(1,1-methyl-6-tert-butylphenol]. 3,3-Tetramethylbutyl)phenol, 2-(2H-benzotriazol-2-yl)-4-methyl-6-(3,4,5,6-tetrahydrophthalimidemethyl)phenol, the reaction product of methyl 3-(3-(2H-benzotriazol-2-yl)-5-tert-butyl-4-hydroxyphenyl)propionate with polyethylene glycol 300, 2-(2H-benzotriazol-2-yl)-6-(linear and branched dodecyl)-4-methylphenol, 2-(5-methyl-2-hydroxyphenyl)benzotriazole, 2-[2-hydroxy-3,5-bis(α,α-dimethylbenzyl)phenyl]-2H-benzotriazole, 3-(2H-benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy-C7-9 branched and linear alkyl esters.

[0385] Among these, benzotriazole compounds with a molecular weight of 400 or higher are preferred. For example, commercially available products include Kemisorb 2792 (manufactured by CHEMIPRO Chemicals), ADK STAB LA31 (manufactured by ADEKA Co., Ltd.), and Tinuvin 234 (manufactured by BASF).

[0386] Examples of benzotriazine compounds include 2-mono(hydroxyphenyl)-1,3,5-triazine compounds, 2,4-bis(hydroxyphenyl)-1,3,5-triazine compounds, and 2,4,6-tris(hydroxyphenyl)-1,3,5-triazine compounds. Specifically, examples include 2,4-diphenyl-6-(2-hydroxy-4-methoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-6-(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4-diphenyl-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, and 2,4-diphenyl-6-(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine. 2,4-Diphenyl-6-(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4-Diphenyl-6-(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4-Diphenyl-6-(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4-Diphenyl-6-(2-hydroxy-4-benzyloxyphenyl)-1,3,5-triazine, 2,4-Diphenyl-6-(2-hydroxy-4-butoxyethoxy)-1,3,5-triazine, 2,4-bis(2-hydroxy-4-butoxyphenyl)-6-(2,4-dibutoxyphenyl)-1,3-5-triazine, 2,4,6-tris(2-hydroxy-4-methoxyphenyl) Triazine, 2,4,6-tris(2-hydroxy-4-ethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-propoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-... Benzyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-ethoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-propoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-methoxycarbonylpropoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-ethoxycarbonylethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-4-(1-(2-ethoxyhexyloxy)-1-oxopropane-2-yloxy)phenyl)-1,3,5-triazine, 2,4,6-Tris(2-hydroxy-3-methyl-4-methoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-propoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6 -Tris(2-hydroxy-3-methyl-4-butoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-hexyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-octyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-dodecyloxyphenyl)-1,3,5-triazine, 2,4,6 -Tris(2-hydroxy-3-methyl-4-benzyloxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-butoxyethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-propoxyethoxyphenyl)-1,3,5- Triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-methoxycarbonylpropoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-ethoxycarbonylethoxyphenyl)-1,3,5-triazine, 2,4,6-tris(2-hydroxy-3-methyl-4-(1-(2-ethoxyhexyloxy)-1-oxopropane-2-yloxy)phenyl)-1,3,5-triazine, etc.

[0387] As benzotriazine compounds, commercially available products can be used, such as Kemisorb102 (manufactured by Kemipro Chemical Co., Ltd.), LA-F70 (manufactured by ADEKA Co., Ltd.), LA-46 (manufactured by ADEKA Co., Ltd.), Tinuvin405 (manufactured by BASF), Tinuvin460 (manufactured by BASF), Tinuvin479 (manufactured by BASF), Tinuvin1577FF (manufactured by BASF), etc.

[0388] Among them, from the perspective of high compatibility with acrylic resins and excellent ultraviolet absorption characteristics, ultraviolet absorbers with a 2,4-bis(2,4-dimethylphenyl)-6-[2-hydroxy-4-(3-alkoxy-2-hydroxypropoxy)-5-α-cumylphenyl]-s-triazine skeleton are further preferred ("alkoxy" refers to long-chain alkoxy such as octoxy, nonoxy, and decoxy).

[0389] As a UV absorber, benzotriazole compounds and benzotriazine compounds with a molecular weight of 400 or more are preferred, especially from the viewpoint of compatibility with resin and volatility upon heating. Furthermore, from the viewpoint of suppressing decomposition caused by heating during the extrusion processing of the UV absorber itself, benzotriazine compounds are particularly preferred.

[0390] In addition, the melting point (Tm) of the above-mentioned ultraviolet absorber is preferably 80°C or higher, more preferably 100°C or higher, even more preferably 130°C or higher, and even more preferably 160°C or higher.

[0391] When the ultraviolet absorber is heated from 23°C to 260°C at a rate of 20°C / minute, the weight reduction rate is preferably 50% or less, more preferably 30% or less, even more preferably 15% or less, even more preferably 10% or less, and even more preferably 5% or less.

[0392] These ultraviolet absorbers can be used alone or in combination of two or more. By combining two ultraviolet absorbers with different structures, it is possible to absorb ultraviolet light over a wide wavelength range.

[0393] The content of the aforementioned ultraviolet absorber is not particularly limited as long as it does not hinder the heat resistance, damp heat resistance, thermal stability, and molding processability while achieving the effects of the present invention. It is preferably 0.1 to 5% by mass relative to 100% by mass of the methacrylic resin, more preferably 0.2 to 4% by mass or less, more preferably 0.25 to 3% by mass, and even more preferably 0.3 to 3% by mass. Within this range, an excellent balance is achieved in ultraviolet absorption performance, molding properties, etc.

[0394] --Mold Release Agent--

[0395] The resin composition constituting the light guide of the head-mounted display in this embodiment may contain a release agent. Examples of such release agents include, but are not limited to, fatty acid esters, fatty acid amides, fatty acid metal salts, hydrocarbon lubricants, alcohol lubricants, polyalkylene glycols, carboxylic acid esters, and hydrocarbon alkane mineral oils.

[0396] There are no particular limitations on the fatty acid esters that can be used as the aforementioned release agents; conventionally known fatty acid esters can be used.

[0397] As fatty acid esters, for example, ester compounds can be made of fatty acids with 12 to 32 carbon atoms, such as lauric acid, palmitic acid, heptadecanic acid, stearic acid, oleic acid, arachidic acid, and betaine, with monovalent aliphatic alcohols such as palmitol, stearyl alcohol, and betaine, or polyvalent aliphatic alcohols such as glycerol, pentaerythritol, dipentaerythritol, and sorbitan; or complex ester compounds of fatty acids and polyvalent organic acids with monovalent or polyvalent aliphatic alcohols.

[0398] Examples of such fatty acid esters include, for example, hexadecyl palmitate, butyl stearate, stearyl stearate, stearyl citrate, glyceryl monocaprylate, glyceryl monodecanoate, glyceryl monolaurate, glyceryl monopalmitate, glyceryl dipalmitate, glyceryl monostearate, glyceryl distearate, glyceryl tristearate, glyceryl monooleate, glyceryl dioleate, glyceryl trioleate, glyceryl monolinoleate, glyceryl monobehenate, glyceryl mono-12-hydroxystearate, glyceryl di-12-hydroxystearate, glyceryl tri-12-hydroxystearate, glyceryl diacetyl monostearate, glyceryl citrate fatty acid ester, pentaerythritol adipate stearate, partially saponified lignite ester, pentaerythritol tetrastearate, dipentaerythritol hexastearate, sorbitan tristearate, etc.

[0399] These fatty acid esters can be used alone or in combination of two or more.

[0400] As commercially available products, examples include the RIKEMAL series, POEM series, RIKEESTAR series, RIKEMASTER series manufactured by Riken Vita, the EXCEL series, RHEODOL series, EXCEPARL series, and COCONAD series manufactured by Kao Corporation. More specifically, examples include the RIKEMAL S-100, RIKEMAL H-100, and POEM series. RIKEMAL S-200 (リケマールS-200), POEM B-200 (ポエムB-200), RIKESTAR EW-200 (リケスターEW-200), RIKESTAR EW-400(リケスターEW-400), EXCEL S-95(エキセルS-95), RHEODOL MS-50(レオドールMS-50), etc.

[0401] There are no particular restrictions on fatty acid amides; previously known fatty acid amides can be used.

[0402] Examples of fatty acid amides include, for instance, saturated fatty acid amides such as lauryl amide, palmitamide, stearamide, benzyl amide, and hydroxystearamide; unsaturated fatty acid amides such as oleamide, erucamide, and castor oil amide; substituted amides such as N-stearylstearamide, N-oleyloleamide, N-stearyloleamide, N-oleylstearamide, N-stearylerucamide, and N-oleylpalmitamide; hydroxymethyl amides such as hydroxymethylstearamide and hydroxymethylbenzyl amide; and methylene bis-stearamide, ethylene bis-decanoamide, ethylene bis-laurateamide, and ethylene bis-stearamide (ethylene bis-stearamide). Dimethyl bis-stearamide, ethylene bisisostearamide, ethylene bishydroxystearamide, ethylene bis-sorbic acid amide, hexamethylene bis-stearamide, hexamethylene bis-sorbic acid amide, hexamethylene bishydroxystearamide, N,N'-distearate adipamide, N,N'-distearate sebacic acid amide and other saturated fatty acid diamides; ethylene bisoleamide, hexamethylene bisoleamide, N,N'-dioletear adipamide, N,N'-dioletear sebacic acid amide and other unsaturated fatty acid diamides; m-xylyl bis-stearamide, N,N'-distearate isophthalic acid amide and other aromatic diamides, etc.

[0403] These fatty acid amides can be used alone or in combination of two or more.

[0404] As commercially available products, examples include the DIAMIDO series (manufactured by Nippon Chemical Co., Ltd.), amide series (manufactured by Nippon Chemical Co., Ltd.), Nikka Amide series (manufactured by Nippon Chemical Co., Ltd.), hydroxymethylamide series, diamide series, Suripakkusu series (manufactured by Nippon Chemical Co., Ltd.), Kao wax series (manufactured by Kao Corporation), fatty acid amide series (manufactured by Kao Corporation), and ethylene bis-stearamides (manufactured by Daiichi Chemical Co., Ltd.).

[0405] Fatty acid metal salts refer to metal salts of higher fatty acids, such as lithium stearate, magnesium stearate, calcium stearate, calcium laurate, calcium ricinoleate, strontium stearate, barium stearate, barium laurate, barium ricinoleate, zinc stearate, zinc laurate, zinc ricinoleate, zinc 2-ethylhexanoate, lead stearate, dilead stearate, lead naphthenate, calcium 12-hydroxystearate, lithium 12-hydroxystearate, etc. Among these, calcium stearate, magnesium stearate, and zinc stearate are particularly preferred from the perspective of making the obtained transparent resin composition have excellent processability and extremely excellent transparency.

[0406] As commercially available products, examples include the SZ series, SC series, SM series, and SA series manufactured by Sakai Chemical Industry Co., Ltd.

[0407] When using the above-mentioned fatty acid metal salt, from the viewpoint of maintaining transparency, the content is preferably 0.2% by mass or less relative to 100% by mass of the resin composition.

[0408] The above-mentioned release agents can be used alone or in combination with two or more.

[0409] As a release agent for use, a release agent with a decomposition start temperature of 200°C or higher is preferred. Here, the decomposition start temperature can be determined by the temperature at which 1% mass is reduced based on TGA.

[0410] The amount of mold release agent should be sufficient to achieve the desired effect. Excessive amounts may cause problems such as seepage during processing or poor extrusion due to screw slippage. Therefore, relative to 100% by mass of the methacrylic resin, it is preferably 5% by mass or less, more preferably 3% by mass or less, further preferably 1% by mass or less, even more preferably 0.8% by mass or less, even more preferably 0.01 to 0.8% by mass, and particularly preferably 0.01 to 0.5% by mass. When added in amounts within the above range, there is a tendency to suppress poor mold release during injection molding while suppressing the decrease in transparency caused by the addition of the mold release agent; therefore, the above conditions are preferred.

[0411] -Other thermoplastic resins-

[0412] The resin composition constituting the light guide of the head-mounted display in this embodiment may contain other thermoplastic resins besides methacrylic resins for the purpose of adjusting birefringence and improving flexibility, as long as it does not impair the purpose of the present invention.

[0413] Other thermoplastic resins include, for example, polyacrylates such as polybutyl acrylate; styrene-based polymers such as polystyrene, styrene-methyl methacrylate copolymers, styrene-butyl acrylate copolymers, styrene-acrylonitrile copolymers, and acrylonitrile-butadiene-styrene block copolymers; in addition, examples include, acrylic rubber particles with a 3- to 4-layer structure disclosed in Japanese Patent Application Publication Nos. 59-202213, 63-27516, 51-129449, and 52-56150; rubbery polymers disclosed in Japanese Patent Application Publication Nos. 60-17406 and 8-245854; and graft copolymer particles containing methacrylic acid rubber obtained by multi-stage polymerization disclosed in International Publication No. 2014-002491; etc.

[0414] From the viewpoint of obtaining good optical and mechanical properties, styrene-acrylonitrile copolymers and rubber-containing graft copolymer particles with grafted portions on the surface layer are preferred, wherein the grafted portions are composed of a composition that is compatible with a methacrylic resin containing a structural unit X having a ring structure on the main chain.

[0415] From the viewpoint of improving the impact strength and optical properties of the film obtained from the composition of this embodiment, the average particle size of the aforementioned acrylic rubber particles, methacrylic rubber graft copolymer particles, and rubber polymer is preferably 0.03 to 1 μm, and more preferably 0.05 to 0.5 μm.

[0416] As for the content of other thermoplastic resins, when the methacrylic resin is set to 100% by mass, it is preferably 0 to 50% by mass, more preferably 0 to 25% by mass.

[0417] [Method for manufacturing the resin composition]

[0418] As for the method of manufacturing the resin composition constituting the light guide of the head-mounted display according to this embodiment, there are no particular limitations as long as a composition that satisfies the conditions of the present invention can be obtained. For example, methods of mixing using a mixing machine such as an extruder, heated roller, kneader, roller mixer, or Banbury mixer can be cited. Among these, mixing based on an extruder is preferred from the perspective of productivity. The mixing temperature can be based on the preferred processing temperature of the polymer constituting the methacrylic resin and the other mixed resins, and can be in the range of 140 to 300°C, preferably in the range of 180 to 280°C. In addition, to reduce volatile components, it is preferable to provide a vent in the extruder.

[0419] Here, in the resin composition constituting the light guide of the head-mounted display in this embodiment, the residual solvent amount (residual solvent amount) is preferably less than 1000 ppm by mass, more preferably less than 800 ppm by mass, and even more preferably less than 700 ppm by mass.

[0420] Here, residual solvent refers to the polymerization solvent used during polymerization (excluding alcohols) and the solvent used when dissolving and solvating the resin obtained by polymerization. Specifically, examples of polymerization solvents include aromatic hydrocarbons such as toluene, xylene, ethylbenzene, and cumene; ketones such as methyl isobutyl ketone, butyl cellosolve, methyl ethyl ketone, and cyclohexanone; and polar solvents such as dimethylformamide and 2-methylpyrrolidone. Examples of solvents used for redissolution include toluene, methyl ethyl ketone, and dichloromethane.

[0421] Regarding the resin composition constituting the light guide of the head-mounted display in this embodiment, the residual alcohol content (residual alcohol content) is preferably less than 500 ppm by mass, more preferably less than 400 ppm by mass, and even more preferably less than 350 ppm by mass.

[0422] Here, residual alcohol refers to alcohols produced as byproducts of cyclization condensation reactions, specifically including aliphatic alcohols such as methanol, ethanol, and isopropanol.

[0423] The amounts of residual solvent and residual alcohol mentioned above can be determined by gas chromatography.

[0424] When choosing any method, it is preferable to prepare the composition while minimizing oxygen and water.

[0425] For example, the dissolved oxygen concentration in the polymerization solution during solution polymerization is preferably less than 300 ppm during the polymerization process. Furthermore, in preparation methods using extruders or the like, the oxygen concentration within the extruder is preferably less than 1% by volume, and more preferably less than 0.8% by volume. The moisture content of the methacrylic resin is preferably adjusted to 1000 ppm by mass or less, and more preferably to 500 ppm by mass or less.

[0426] As long as these ranges are within which it is relatively easy to prepare compositions that meet the necessary conditions of the present invention, it is therefore advantageous.

[0427] [Manufacturing method of resin light guide for head-mounted displays]

[0428] The resin light guide for a head-mounted display according to this embodiment is formed by molding the above-described resin composition. As a method for manufacturing the resin light guide for a head-mounted display according to this embodiment, molding methods such as injection molding, compression molding, and extrusion molding can be used. From a productivity point of view, injection molding is preferred.

[0429] Typically, injection molding consists of the following steps: (1) Injection step, where resin is melted and filled into the cavity of a temperature-controlled mold; (2) Pressure holding step, where pressure is applied into the cavity until the gate is sealed, and an amount of resin equivalent to the amount of molten resin filled in the injection step is injected into the mold to cool and shrink upon contact with the mold; (3) Cooling step, where the molded part is held until the resin is cooled after the pressure holding is released; and (4) Step of opening the mold and removing the cooled molded part.

[0430] At this point, the molding temperature, based on the glass transition temperature (Tg) of the resin composition, can be in the range of Tg+100℃ to Tg+160℃, preferably in the range of Tg+110℃ to Tg+150℃. Here, molding temperature refers to the controlled temperature of the heating element wound around the injection nozzle. Higher molding temperatures result in resin-based light guides with lower phase differences, but high temperatures also promote coloration due to thermal degradation during residence in the molding machine; therefore, it is necessary to select the molding temperature appropriately.

[0431] Furthermore, the mold temperature is based on the glass transition temperature (Tg) of the resin composition, preferably in the range of Tg-70℃ to Tg, and more preferably in the range of Tg-50℃ to Tg-20℃.

[0432] In addition, the injection speed can be appropriately selected according to the thickness and size of the resin light guide to be obtained, for example, it can be appropriately selected in the range of 10 to 1000 mm / s.

[0433] In addition, the pressure used for holding the pressure can be appropriately selected according to the shape of the resin light guide to be obtained, for example, it can be appropriately selected in the range of 30 to 120 MPa.

[0434] Here, the pressure used for holding pressure refers to the pressure maintained after the molten resin has been filled, by a screw used to further deliver the molten resin from the gate.

[0435] In addition, an annealing process can be performed to alleviate residual stress caused by injection molding and reduce the phase difference of the resin light guide. Regarding the annealing temperature, based on the glass transition temperature (Tg) of the resin composition, it is preferably in the range of Tg-50℃ to Tg, and more preferably in the range of Tg-30℃ to Tg-10℃.

[0436] The surface of the resin light guide for the head-mounted display of this embodiment may be further functionalized, for example, by hard coating, anti-reflection treatment, transparent conductive treatment, electromagnetic wave shielding treatment, gas barrier treatment, etc. The thickness of these functional layers is not particularly limited, and is typically in the range of 0.01 to 10 μm.

[0437] As a hard coating layer applied to its surface, for example, a coating liquid made by dissolving or dispersing a silicone-based curable resin, a curable resin containing organic polymer composite inorganic particles, urethane acrylate, epoxy acrylate, polyfunctional acrylate, or other acrylate and a photopolymerization initiator in an organic solvent is applied to a film or plate obtained from the resin composition of this embodiment using a conventionally known coating method, dried, and then photocured to form the coating.

[0438] In addition, to improve adhesion, for example, a method can be used to form a hard coating layer after pre-setting an easy-to-adhere layer, a primer layer, an anchoring layer, etc., whose components contain inorganic microparticles, before applying the hard coating layer.

[0439] As an anti-glare layer on its surface, particles such as silica, melamine resin, and acrylate resin are inkd and coated onto other functional layers using conventional coating methods, and then thermo-cured or photo-cured to form the layer.

[0440] Examples of antireflective layers applied to their surfaces include thin films composed of inorganic materials such as metal oxides, fluorides, silicides, borides, nitrides, and sulfides; single or multilayer antireflective layers composed of resins with different refractive indices, such as acrylate resins and fluororesins; and antireflective layers formed by stacking thin layers of composite microparticles containing inorganic and organic compounds.

[0441] [Example]

[0442] The present invention will now be described in detail with examples and comparative examples. It should be noted that the present invention is not limited to the following examples.

[0443] <1. Determination of the amount of 2-cyclohexylamino-N-cyclohexylsuccinimide in N-cyclohexylmaleimide>

[0444] N-cyclohexylmaleimide or N-cyclohexylmaleimide / m-xylene solution was collected and weighed to prepare a 25% by mass N-cyclohexylmaleimide m-xylene solution. Isopropyl benzoate was added as an internal standard. The determination was carried out using a gas chromatograph (Shimadzu Corporation, GC-2014) under the following conditions.

[0445] Detector: FID.

[0446] Chromatographic column used: HP-5ms.

[0447] Measurement conditions: After holding at 80℃ for 5 minutes, the temperature was increased to 300℃ at a rate of 10℃ / minute, and then held for 5 minutes.

[0448] <2. Determination of the amount of 2-aniline-N-phenylsuccinimide in N-phenylmaleimide>

[0449] Collect and weigh N-phenylmaleimide or N-phenylmaleimide / m-xylene solution to prepare a 10% by mass N-phenylmaleimide m-xylene solution. Add isopropyl benzoate as an internal standard and determine the N-phenylmaleimide solution using a liquid chromatograph (Waters Corporation, UPLC H-class) under the following conditions.

[0450] Detector: PDA (detection wavelength: 210nm~300nm).

[0451] Column used: ACQUITY UPLC HSS T3.

[0452] Column temperature: 40℃.

[0453] Mobile phase: 50% aqueous solution of acetonitrile containing 0.1% formic acid.

[0454] Flow rate: 0.4 mL / min.

[0455] <3. Determination of the residual amount of N-substituted maleimide monomer>

[0456] A portion of the analyte (polymerized solution or methacrylic resin particles) was collected and weighed. This sample was dissolved in chloroform to prepare a 5% by mass solution. n-Decane was added as an internal standard. The determination was performed using a gas chromatograph (Shimadzu Corporation, GC-2010) under the following conditions.

[0457] Detector: FID.

[0458] Chromatographic column used: ZB-1.

[0459] Measurement conditions: After holding at 45℃ for 5 minutes, the temperature was increased to 300℃ at a rate of 20℃ / min, and then held for 15 minutes.

[0460] <4. Analysis of Structural Units>

[0461] The structural units in the methacrylic resins manufactured in the manufacturing examples and comparative examples described below, unless otherwise stated, are derived by means of... 1 H-NMR measurements and 13 C-NMR determination was used to identify the structural units of methacrylic resins and methacrylic resin compositions, and to calculate their amounts. 1 H-NMR measurements and 13 The measurement conditions for C-NMR are as follows.

[0462] • Measuring equipment: JNM-ECZ400S manufactured by Nippon Electronics Co., Ltd.

[0463] • Solvent for determination: CDCl3 or d6-DMSO.

[0464] • Measurement temperature: 40℃.

[0465] <5. Molecular weight and molecular weight distribution>

[0466] The weight-average molecular weight (Mw), number-average molecular weight (Mn), and Z-average molecular weight (Mz) of the methacrylic resin compositions manufactured in the manufacturing examples and comparative examples described below were determined using the apparatus and conditions described below.

[0467] • Apparatus used for measurement: Gel permeation chromatography (HLC-8320GPC) manufactured by Tosoh Corporation.

[0468] • Measurement conditions:

[0469] Chromatographic columns: Use one TSKguardcolumn SuperH-H, two TSKgel SuperHM-M, and one TSKgel SuperH2500 in series.

[0470] Column temperature: 40℃.

[0471] Developing solvent: tetrahydrofuran; flow rate: 0.6 mL / min; 2,6-di-tert-butyl-4-methylphenol (BHT) was added at 0.1 g / L as an internal standard.

[0472] Detector: RI (Differential Refraction) detector.

[0473] Detection sensitivity: 3.0 mV / min.

[0474] Sample: 20 mL of tetrahydrofuran solution containing 0.02 g of a methacrylic resin composition.

[0475] Injection volume: 10 μL.

[0476] Standard samples for calibration curves: Ten polymethyl methacrylates (PMMA Calibration Kit MM-10) with known and different molecular weights and monodisperse gravimetric peaks were used.

[0477] Weight peak molecular weight (Mp)

[0478] Standard sample 2 625,500 Standard sample 3 298,900 Standard sample 4 138,600 Standard sample 5 60,150 Standard sample 6 27,600 Standard sample 7 10,290 Standard sample 8 5,000 Standard sample 9 2,810 Standard sample 10 850

[0479] Under the above conditions, the RI detection intensity relative to the elution time of the methacrylic resin composition was determined.

[0480] Based on the calibration curves obtained by measuring standard samples using the above calibration curves, the weight-average molecular weight (Mw), number-average molecular weight (Mn), and Z-average molecular weight (Mz) of the methacrylic resin composition are determined, and their values ​​are used to determine the molecular weight distribution (Mw / Mn) and (Mz / Mw).

[0481] <6. In-plane phase difference of resin light guides>

[0482] Using the incident surface of the image light of the light guide obtained from the examples and comparative examples as the observation surface, the phase difference distribution of the light guide was measured by using a PA-200-L birefringence evaluation system manufactured by Photonic Lattice, Inc. with a wavelength of 520 nm through the incident surface. The area within the surface of the light guide was specified, and the average value (nm) of the absolute value of the phase difference was calculated.

[0483] <7. Content of fluorescent light-emitting substances in resin-based light guides>

[0484] The resin light guides obtained from the examples and comparative examples were finely cut, weighed into glass sample vials, and chloroform was added. The solution was shaken at 800 times per minute for 30 minutes using a shaker to prepare a 2.0% by mass chloroform solution of the resin light guides. The fluorescence intensity was measured using a fluorescence spectrophotometer (Manufactured by Horiba Jobin Yvon Co., Ltd., Fluorolog 3-22).

[0485] Regarding the measurement conditions, a xenon lamp was used as the light source, a PMT was used as the detector, the excitation wavelength was 436 nm, the slit width was set to 2 nm on both the excitation and observation sides, the time constant was 0.2 s, the measurement mode was to normalize the luminous intensity by the excitation light intensity at each wavelength using the Sc / Rc ratio, and the measurement was performed by observing at 90° using a quartz cuvette with an optical path length of 1 cm.

[0486] The fluorescence intensity at the obtained wavelength of 530 nm was normalized using the fluorescence intensity of the fluorescein / ethanol solution. Specifically, as described below.

[0487] Find the values ​​for ethanol and 5×10 -8 mol / L and 1×10 -6 The fluorescence intensity at 530 nm of a mol / L fluorescein / ethanol solution under spectral analysis at an excitation wavelength of 436 nm was subtracted from the ethanol blank, and a concentration-intensity conversion formula was constructed. The fluorescence emission spectrum of chloroform was measured. The emission intensity at 530 nm was obtained by subtracting the emission intensity of chloroform at 530 nm from the emission intensity of a 2.0% (w / w) resin-based chloroform guide solution. The concentration was then calculated using the previously derived concentration-intensity conversion formula for the fluorescein / ethanol solution, and the content of the fluorescent luminescent substance (mol / L) was determined.

[0488] <8. Glass transition temperature of resin light guides>

[0489] According to JIS-K7121, the glass transition temperature (Tg) (°C) of resin light guides was determined.

[0490] First, as a test piece, approximately 10 mg of resin light guide material was cut from four points (four locations) at standard conditions (23°C, 50% RH) after being conditioned (placed at 23°C for 1 week).

[0491] Next, using a differential scanning calorimeter (PerkinElmer Japan Ltd., Diamond DSC) at a nitrogen flow rate of 25 mL / min, the sample was heated from room temperature (23°C) to 200°C at a rate of 10°C / min (single heating), held at 200°C for 5 minutes to allow complete melting, then cooled from 200°C to 40°C at a rate of 10°C / min, held at 40°C for 5 minutes, and then further heated under the same conditions (second heating). The glass transition temperature (Tg) (°C) was determined by intersecting the step-like change curve during the second heating with a straight line equidistant from the extended baselines along the vertical axis at the midpoint of the curve. Four measurements were taken for each sample, and the arithmetic mean of the four measurements (rounded to the nearest decimal) was taken as the measured value.

[0492] <9. Photoelastic coefficient of resin light guides>

[0493] After finely cutting the resin light guide obtained from the examples and comparative examples, a vacuum compression molding machine was used to make a mold, which was then used as a test sample.

[0494] As for specific sample preparation conditions, a vacuum compression molding machine (SFV-30 type, manufactured by Shinto Metal Industries, Ltd.) was used. After preheating at 260°C and under reduced pressure (approximately 10 kPa) for 10 minutes, the resin light guide was compressed at 260°C and approximately 10 MPa for 5 minutes. After releasing the reduced pressure and compression, the sample was transferred to a cooling compression molding machine for cooling and curing. The resulting mold was cured in a constant temperature and humidity chamber at 23°C and 60% for at least 24 hours. Based on this, test pieces (approximately 150 μm thick and 6 mm wide) were cut out for measurement.

[0495] The photoelastic coefficient C was measured using a birefringence measuring apparatus detailed in *Polymer Engineering and Science* (1999, 39, 2349-2357). R (Pa -1 ).

[0496] The film test piece was placed in a film stretching apparatus (manufactured by Imoto Manufacturing Co., Ltd.) also located in a constant temperature and humidity chamber, with the clamp spacing being 50 mm. Next, the apparatus was configured such that the laser beam of the birefringence measuring device (manufactured by Otsuka Electronics, RETS-100) was located at the center of the film, and tensile stress was applied at a deformation rate of 50% / min (clamp spacing: 50 mm, clamp movement speed: 5 mm / min), while the birefringence of the test piece was measured.

[0497] The birefringence (Δn) and tensile stress (σ) obtained from the measurement R The relationship between the two is used to determine the slope of the straight line through the least squares approximation, and the photoelastic coefficient (C) is then calculated. R (Pa) -1 In the calculations, a tensile stress of 2.5 MPa ≤ σ is used. R Data between ≤10MPa.

[0498] C R =Δn / σ R

[0499] Here, birefringence (Δn) is given by the values ​​shown below.

[0500] Δn=nx-ny

[0501] (nx: refractive index in the stretching direction, ny: refractive index in the plane perpendicular to the stretching direction)

[0502] <10. Light transmittance of resin light guides>

[0503] For the resin light guides obtained from the examples and comparative examples, the surface containing the image light incident on was taken as the incident surface. Using a spectrophotometer (manufactured by Nippon Denshoku Kogyo Co., Ltd., SD-5000), the transmittance (%) was measured every 5 nm in the wavelength range of 380–780 nm with a D65 light source and a 10° field of view. Using the measured values, the ratio (T450 / T680) of the transmittance at wavelength 450 nm (T450) to the transmittance at wavelength 680 nm (T680) was calculated.

[0504] <11. Image Clarity>

[0505] Using the resin light guide obtained from the examples and comparative examples, reflective volumetric holographic diffraction gratings were adhered to the opposite sides of the incident portion (incident surface) of the image light and the exit portion (emission surface) of the display light, respectively, to fabricate a... Figure 1 The evaluation system shown.

[0506] This evaluation system is formed by combining a display device 1, a collimating lens 2, a light guide 3, a first reflective volume hologram 4, and a second reflective volume hologram 5. Light from any position on the display device 1 is collimated by the collimating lens 2, then enters the light guide 3. Its direction is changed by diffraction through the first reflective volume hologram 4, and it is guided within the light guide by total internal reflection. The guided light reaches the second reflective volume hologram 5, where it is diffracted again and enters the observer's pupil 6.

[0507] It should be noted that, in Figure 1 In the image, the direction of the image light is taken as the X-axis by the collimator lens 2 to make it parallel light, and the light guide 3 is set as the incident surface to become the YZ plane.

[0508] A still image of blue monochrome is projected from display device 1. The sharpness of the image when viewed at the position of the observer's pupil 6 is evaluated according to the following evaluation criteria.

[0509] [Evaluation Criteria]

[0510] Image clarity

[0511] 〇: No bleeding or blurring is observed in the image.

[0512] △: Due to color bleeding and blurring, the image becomes slightly unclear, but it is still possible to identify what image is being projected.

[0513] ×: Due to color bleeding and blurring, the image becomes unclear, making it impossible to identify what image is being projected.

[0514] Tone reproduction

[0515] 〇: Clearly reproduces the blue color.

[0516] ×: The reproduction of blue is worse.

[0517] [raw material]

[0518] The raw materials used in the embodiments and comparative examples described below are as follows.

[0519] [[monomer]]

[0520] ·Methyl methacrylate (MMA): manufactured by Asahi Kasei Co., Ltd.

[0521] • N-Cyclohexylmaleimide (chMI): Nippon Shokubai Co., Ltd.

[0522] (The mass ratio of 2-cyclohexylamino-N-cyclohexylsuccinimide (CCSI) relative to the chMI mass is 80 ppm by mass)

[0523] • N-Phenylonmaleimide (phMI): Nippon Shokubai Co., Ltd.

[0524] (The mass ratio of 2-aniline-N-phenylsuccinimide (APSI) relative to the phMI mass is 60 ppm)

[0525] Pretreatment of -N-substituted maleimides (chMI, phMI) (washing and dehydration steps) - The above-mentioned N-cyclohexylmaleimide (chMI) and N-phenylmaleimide (phMI) are subjected to the following washing and dehydration steps to remove 2-amino-N-substituted succinimide (CCSI, APSI) and moisture.

[0526] --Washing and dehydration of N-cyclohexylmaleimide (chMI)--

[0527] ---Reduce CCSI in N-cyclohexylmaleimide to below 5 ppm by mass---

[0528] Measure 250.0 kg of CHMI and 750.0 kg of m-xylene (hereinafter referred to as "mXy") and add them to a 2.0 m³ container equipped with a temperature control device based on a jacket and three swept blades serving as stirring blades. 3 A glass-lined reactor was used. Steam was blown into the reactor's jacket to raise the temperature of the solution inside to 56°C, and the mixture was stirred to obtain an organic layer. Next, 350.0 kg of 2% sulfuric acid solution was measured and added to the reactor. The solution temperature was maintained at 56°C, and the mixture was stirred at 100 rpm for 10 minutes. Stirring was then stopped, and the mixture was allowed to stand for 10 minutes before the aqueous layer was pumped into a cylindrical tank.

[0529] The same procedure was repeated twice more, and the organic layer was washed with sulfuric acid solution a total of three times. The CCSI content in the organic layer was quantified using gas chromatography, and the result was 4.9 ppm by mass relative to the chMI in the organic layer.

[0530] Subsequently, 350.0 kg of ion-exchanged water was added to the reactor, the solution temperature was maintained at 55°C, and the mixture was stirred at 100 rpm for 10 minutes. Stirring was then stopped, and the mixture was allowed to stand for 20 minutes before the water layer was pumped into a cylindrical tank.

[0531] The same procedure was repeated once more, and the organic layer was washed with ion-exchanged water twice. The CCSI level in the organic layer was quantified by gas chromatography, and the result was 4.6 ppm by mass relative to the chMI in the organic layer.

[0532] Next, the solution temperature was maintained at 50°C, and the pressure inside the reactor was gradually reduced to 5 kPa while stirring at 100 rpm. Afterward, the solution temperature was raised to 60°C for azeotropic dehydration. 131.6 kg of water / mXy mixture was removed by distillation, and the water concentration in the organic layer was quantified using a Karl Fischer moisture analyzer, yielding a result of 102 ppm relative to the mass of the organic layer.

[0533] Adding concentration-adjusting agent mXy to the organic layer yielded 1034.3 kg of an organic layer with a chMI of 24.0 wt%, a moisture concentration of 191 ppm wt%, and a CCSI relative to chMI of 4.6 ppm wt.

[0534] ---Reduce CCSI in N-cyclohexylmaleimide to below 1 ppm by mass---

[0535] Measure 80.0 kg of chMI and 240.0 kg of mXy, and add them to a 0.50 m³ full zone of Kobelco Environmental Solutions, which is equipped with a temperature control device based on a jacket and stirring blades. 3 A glass-lined reactor was used. Steam was blown into the reactor's jacket to raise the temperature of the solution inside to 55°C, and the mixture was stirred to obtain an organic layer. Next, 112.0 kg of 2% sulfuric acid solution was measured and added to the reactor. The solution temperature was maintained at 55°C, and the mixture was stirred at 100 rpm for 30 minutes. Stirring was stopped, and the mixture was allowed to stand for 10 minutes before the aqueous layer was pumped into a cylindrical tank.

[0536] The same operation was repeated three more times, and the organic layer was washed with sulfuric acid solution a total of four times. The CCSI content in the organic layer was quantified using gas chromatography, and the result was 0.57 ppm by mass relative to the chMI in the organic layer.

[0537] Subsequently, 112.0 kg of ion-exchanged water was added to the reactor, the solution temperature was maintained at 55°C, and the mixture was stirred at 100 rpm for 30 minutes. Stirring was then stopped, and the mixture was allowed to stand for 10 minutes before the water layer was pumped out to a cylindrical tank.

[0538] The solution temperature was maintained at 50°C, and the pressure inside the reactor was gradually reduced to 5 kPa while stirring at 100 rpm. Subsequently, the solution temperature was raised to 60°C for azeotropic dehydration. 54 kg of water / m³y mixture was removed by distillation, and the water concentration in the organic layer was quantified using a Karl Fischer moisture analyzer, yielding a result of 46 ppm relative to the mass of the organic layer.

[0539] Adding concentration-adjusting agent mXy to the organic layer yielded 384.0 kg of an organic layer with a chMI of 20.3% by mass, a moisture concentration of 125 ppm by mass, and a CCSI relative to chMI of 0.60 ppm by mass.

[0540] --Washing and dehydration of N-phenylmaleimide (phMI)--

[0541] ---Reduce APSI in N-phenylmaleimide to below 5 ppm by mass---

[0542] Measure 150.0 kg of phMI and 720.0 kg of mXy, and add them to a 2.0 m³ container equipped with a temperature control device based on a jacket and three swept blades serving as stirring blades. 3 In a glass-lined reactor, steam is blown into the jacket to raise the temperature of the solution inside the reactor to 55°C, and stirring is performed to obtain an organic layer. Next, 336.0 kg of 7% sodium bicarbonate solution is measured and added to the reactor, and the solution temperature is maintained at 55°C. The solution is stirred at 100 rpm for 10 minutes. Stirring is stopped, and the mixture is allowed to stand for 10 minutes before the aqueous layer is pumped into a cylindrical tank.

[0543] Next, 336.0 kg of ion-exchanged water was added to the reactor, and the solution temperature was maintained at 55°C. The mixture was stirred at 100 rpm for 10 minutes. After stirring was stopped, the mixture was allowed to stand for 10 minutes, and then the aqueous layer was pumped into a cylindrical tank.

[0544] Subsequently, 336.0 kg of 2% sulfuric acid solution was measured and added to the reactor. The solution temperature was maintained at 55°C, and the mixture was stirred at 100 rpm for 10 minutes. Stirring was then stopped, and the mixture was allowed to stand for 10 minutes before the aqueous layer was pumped into a cylindrical tank.

[0545] Similarly, the rinsing process using ion-exchanged water will be performed twice more.

[0546] The amount of APSI in the organic layer was quantified using liquid chromatography, and the result was 3.6 ppm by mass relative to the phMI in the organic layer.

[0547] Next, the solution temperature was maintained at 50°C, and the pressure inside the reactor was gradually reduced to 5 kPa while stirring at 100 rpm. Afterward, the solution temperature was raised to 55°C for azeotropic dehydration. 190 kg of water / m³y mixture was removed by distillation, and the water concentration in the organic layer was quantified using a Karl Fischer moisture analyzer, yielding a result of 47 ppm relative to the mass of the organic layer.

[0548] Adding concentration-adjusting agent mXy to the organic layer yielded 1340.7 kg of an organic layer with a pH MI of 10.8% by mass, a moisture concentration of 170 ppm by mass, and an APSI relative to the pH MI of 3.4 ppm by mass.

[0549] ---Reduce APSI in N-phenylmaleimide to below 1 ppm by mass---

[0550] Measure 50.0 kg of phMI and 240.0 kg of mXy, and add them to a 0.50 m³ full zone equipped with a sheath-based temperature control device and stirring blades, manufactured by Kobelco Environmental Solutions. 3 In a glass-lined reactor, steam was blown into the jacket to raise the temperature of the solution inside the reactor to 55°C, and stirring was performed to obtain an organic layer. Next, 112.0 kg of 7% sodium bicarbonate solution was measured and added to the reactor, and the solution temperature was maintained at 55°C while stirring at 100 rpm for 15 minutes. Stirring was stopped, and the mixture was allowed to stand for 10 minutes before the aqueous layer was pumped into a cylindrical tank. This same operation was repeated once more, resulting in a total of two washes of the organic layer using sodium bicarbonate solution.

[0551] Next, 112.0 kg of ion-exchanged water was added to the reactor, and the solution temperature was maintained at 55°C. The mixture was stirred at 100 rpm for 30 minutes. Stirring was then stopped, and the mixture was allowed to stand for 10 minutes before the water layer was pumped into a cylindrical tank.

[0552] Subsequently, 112.0 kg of 2% sulfuric acid solution was measured and added to the reactor. The solution temperature was maintained at 55°C, and the mixture was stirred at 100 rpm for 30 minutes. Stirring was stopped, and the mixture was allowed to stand for 10 minutes before the aqueous layer was pumped into a cylindrical tank. This same operation was repeated twice more, for a total of three washes of the organic layer with sulfuric acid solution.

[0553] Similarly, the rinsing process using ion-exchanged water will be performed twice more.

[0554] The amount of APSI in the organic layer was quantified using liquid chromatography, and the result was 0.37 ppm by mass relative to the phMI in the organic layer.

[0555] The solution temperature was maintained at 50°C, and the pressure inside the reactor was gradually reduced to 5 kPa while stirring at 100 rpm. Subsequently, the solution temperature was raised to 55°C for azeotropic dehydration. 72 kg of water / m³y mixture was removed by distillation, and the water concentration in the organic layer was quantified using a Karl Fischer moisture analyzer, yielding a result of 60 ppm relative to the mass of the organic layer.

[0556] A concentration adjustment agent, mXy, was added to the organic layer to obtain an organic layer of 432.8 kg with a pH MI of 10.3% by mass, a moisture concentration of 180 ppm by mass, and an APSI relative to the pH MI of 0.42 ppm by mass.

[0557] Polymerization initiators

[0558] ·1,1-Di(tert-butylperoxide)cyclohexane: manufactured by Nippon Oil Co., Ltd. as “PERHEXA C (パーヘキサC)”.

[0559] Chain transfer agent

[0560] ·N-octylmercaptan: manufactured by Kao Corporation.

[0561] Hindered phenolic antioxidants

[0562] • Irganox 1010: Made by BASF.

[0563] Phosphorus-based antioxidants

[0564] • Irgafos 168 (melting point 180~190℃): manufactured by BASF.

[0565] [Methacrylic acid resin composition]

[0566] [Manufacturing Example 1]

[0567] 374.8 kg of an mXy solution with a pH MI of 10.3% (APSI relative to pH MI: 0.42 ppm) after washing and dehydration processes, and 323.6 kg of an mXy solution with a CH MI of 20.3% (CCSI relative to CH MI: 0.60 ppm) after washing and dehydration processes were measured and added to a 1.25 m³ container equipped with a sheathed temperature control device and stirring blades. 3 In a reactor at a solution temperature of 60°C and an internal pressure of 5 kPa, 160.8 kg of mXy was removed by distillation under reduced pressure while stirring. Next, the reactor was restored to atmospheric pressure, and 16.7 kg of mXy was added, thereby preparing a mixed solution of 38.6 kg of phMI, 65.7 kg of chMI, and 450.0 kg of mXy. 445.7 kg of MMA and 0.413 kg of n-octylthiol (as a chain transfer agent) were measured, added, and stirred to obtain a monomeric mixed solution.

[0568] For the contents of the reactor liquid, nitrogen-based bubbling is carried out at a rate of 30 L / min for 1 hour to remove dissolved oxygen.

[0569] Subsequently, steam was blown into the sheath to raise the temperature of the solution in the reactor to 125°C. While stirring at 50 rpm, 0.23 kg of 1,1-di(tert-butylperoxy)cyclohexane dissolved in 2.77 kg of mXy polymerization initiator solution was added at a rate of 0.5 kg / h to start polymerization. Addition was stopped 6 hours after the start of polymerization.

[0570] It should be noted that the solution temperature in the reactor is controlled at 125±2℃ using sheath-based temperature regulation during polymerization.

[0571] After 8 hours from the start of polymerization, a polymerization solution containing a methacrylic resin with a ring structure on the main chain is obtained.

[0572] The amount of N-substituted maleimide in the obtained polymerization solution was evaluated, and the results included 1340 ppm phMI and 4390 ppm chMI.

[0573] In this polymerization solution, 0.1% by mass of Irganox 1010 and 0.05% by mass of Irgafos168 relative to 100% by mass of the polymer contained in the solution are added under stirring.

[0574] The polymer solution containing this antioxidant is filtered by passing it through a filter with a filtration precision of 2 μm made of SUS316L metal fibers.

[0575] To recover polymer from the polymerization solution, a flat-plate heat exchanger with an internal volume of approximately 0.3 m³ is used as the apparatus for the devolatilization process. This heat exchanger comprises a flat-plate slit-type flow path and a heat medium flow path. 3 A devolatilization device consisting of a pressure-reducing vessel (hereinafter referred to as a devolatilizer) with an attached SUS heating medium jacket.

[0576] A solution containing the polymer obtained through polymerization is fed at a rate of 30 liters per hour to a heat exchanger located above a vacuum vessel. After being heated to 260°C, the solution is fed into a devolatilization tank heated and depressurized to an internal temperature of 260°C and a vacuum degree of 30 Torr for devolatilization treatment. The shear rate within the devolatilization unit is calculated to be 5.3 s based on the device shape and operating conditions. -1 .

[0577] The devolatilized polymer is pressurized from the bottom of the devolatilization tank using a gear pump, extruded from a wire die, water-cooled, and then granulated to obtain methacrylic resin composition A.

[0578] The composition of the methacrylic resin composition A was confirmed, derived from the structural units of the monomers MMA, phMI, and chMI, which were 81.2% by mass, 7.1% by mass, and 11.7% by mass, respectively. Additionally, the weight-average molecular weight (Mw) was 148,000, the Mw / Mn ratio was 2.12, the Mz / Mw ratio was 1.63, and the glass transition temperature was 133°C.

[0579] [Manufacturing Example 2]

[0580] 352.4 kg of an mXy solution with a pH MI of 10.3% (APSI relative to pH MI: 0.42 ppm) after washing and dehydration, and 310.3 kg of an mXy solution with a CH MI of 20.3% (CCSI relative to CH MI: 0.60 ppm) after washing and dehydration, were measured and added to a 1.25 m³ container equipped with a sheathed temperature control device and stirring blades. 3 In a reactor at a solution temperature of 60°C and an internal pressure of 5 kPa, 335.4 kg of mXy was removed by distillation under reduced pressure while stirring. Next, the reactor was restored to atmospheric pressure, and 8.9 kg of mXy was added, thereby preparing a mixed solution of 36.3 kg of phMI, 63.0 kg of chMI, and 236.9 kg of mXy. 340.7 kg of MMA and 0.275 kg of n-octylthiol (as a chain transfer agent) were measured, added, and stirred to obtain a monomeric mixed solution.

[0581] Next, measure 123.1 kg of mXy and add it to container 1.

[0582] In addition, 110.0 kg of MMA and 90.0 kg of mXy were measured and stirred in tank 2 as a supplementary monomer solution.

[0583] For the liquid contents of the reactor, nitrogen-based bubbling was carried out at a rate of 30 L / min for 1 hour, and for each of tanks 1 and 2, nitrogen-based bubbling was carried out at a rate of 10 L / min for 30 minutes to remove dissolved oxygen.

[0584] Subsequently, steam was blown into the jacket to raise the solution temperature in the reactor to 128°C. While stirring at 50 rpm, a polymerization initiator solution of 0.37 kg of 1,1-di(tert-butylperoxide)cyclohexane dissolved in 3.005 kg of mXy was added at a rate of 1 kg / h to initiate polymerization. 0.5 hours after the start of polymerization, the rate of initiator solution addition was reduced to 0.25 kg / h, while mXy was added from tank 1 at a rate of 35.2 kg / h for 3.5 hours.

[0585] It should be noted that the solution temperature in the reactor is controlled at 128±2℃ using sheath-based temperature regulation during polymerization.

[0586] Next, 4 hours after the start of polymerization, the rate of initiator solution addition was changed to 0.75 kg / h, while the monomer solution containing MMA was added from tank 2 at a rate of 100.0 kg / h for 2 hours.

[0587] Furthermore, the initiator solution addition rate was reduced to 0.5 kg / h 6 hours after the start of polymerization, and addition was stopped 7 hours after the start of polymerization. The polymerization was continued for another hour to obtain a polymerization solution containing a methacrylic resin with ring structural units on the main chain.

[0588] The amount of N-substituted maleimide in the obtained polymerization solution was evaluated, and the results included 220 ppm phMI and 1070 ppm chMI.

[0589] In this polymerization solution, 0.1% by mass of Irganox 1010 and 0.05% by mass of Irgafos168 relative to 100% by mass of the polymer contained in the solution are added under stirring.

[0590] The polymer solution containing antioxidants is filtered by passing it through a filter with a filtration precision of 2 μm made of SUS316L metal fibers.

[0591] To recover polymer from the polymerization solution, a flat-plate heat exchanger with an internal volume of approximately 0.3 m³ is used as the apparatus for the devolatilization process. This heat exchanger comprises a flat-plate slit-type flow path and a heat medium flow path. 3 A devolatilization device consisting of a pressure-reducing vessel (hereinafter referred to as a devolatilization tank) with an attached SUS heating medium sheath, wherein the devolatilization device does not have a rotating part.

[0592] A solution containing the polymer obtained through polymerization is fed at a rate of 30 liters per hour to a heat exchanger located above a vacuum vessel. After being heated to 260°C, the solution is fed into a devolatilization tank heated and depressurized to an internal temperature of 260°C and a vacuum degree of 30 Torr for devolatilization treatment. The shear rate within the devolatilization unit is calculated to be 5.3 s based on the device shape and operating conditions. -1 .

[0593] The devolatilized polymer is pressurized from the bottom of the devolatilization tank using a gear pump, extruded from a wire die, water-cooled, and then granulated to obtain methacrylic resin composition B.

[0594] The composition of the methacrylic resin composition B was confirmed, derived from the structural units of the monomers MMA, phMI, and chMI, which were 80.9% by mass, 7.0% by mass, and 12.1% by mass, respectively. Additionally, the weight-average molecular weight (Mw) was 142,000, the Mw / Mn ratio was 2.32, the Mz / Mw ratio was 1.75, and the glass transition temperature was 134°C.

[0595] [Manufacturing Example 3]

[0596] As the phMI after the washing and dehydration processes, 10.8% by mass of mXy solution (APSI is 3.4 ppm by mass relative to phMI) was used, and as the chMI after the washing and dehydration processes, 24.0% by mass of mXy solution (CCSI is 4.6 ppm by mass relative to chMI) was used. The composition of the mixed solution prepared in the reactor was the same as in Manufacturing Example 2. Except for this, the process was carried out in the same manner as in Manufacturing Example 2 to obtain methacrylic resin composition C.

[0597] It should be noted that the evaluation of the amount of N-substituted maleimide in the obtained polymerization solution includes phMI of 210 ppm by mass and chMI of 1090 ppm by mass.

[0598] The composition of the methacrylic resin composition C was confirmed, derived from the structural units of the monomers MMA, phMI, and chMI, which were 80.8% by mass, 7.1% by mass, and 12.1% by mass, respectively. Additionally, the weight-average molecular weight (Mw) was 141,000, the Mw / Mn ratio was 2.31, the Mz / Mw ratio was 1.75, and the glass transition temperature was 134°C.

[0599] [Manufacturing Example 4]

[0600] In a reactor equipped with a jacket-based temperature control device and stirring blades, 40 parts by mass of MMA, 60 parts by mass of mXy, and 0.08 parts by mass of n-octylthiol as a chain transfer agent were charged. Nitrogen-based bubbling was performed for 1 hour to remove dissolved oxygen. Subsequently, steam was blown into the jacket to raise the solution temperature in the reactor to 120°C. While stirring at 50 rpm, a polymerization initiator solution containing 0.02 parts by mass of 1,1-di(tert-butylperoxy)cyclohexane dissolved in 0.10 parts by mass of mXy was added at a constant rate for 5 hours to carry out polymerization. The solution was further matured at 120°C for 3 hours. The polymerization was completed 8 hours after the start of polymerization to obtain a PMMA mXy solution. After polymerization, the liquid temperature was lowered to 50°C.

[0601] Next, a mixture of 12 parts by mass of monomethylamine and 12 parts by mass of methanol was added dropwise to the reactor at room temperature. The liquid temperature was raised to 170°C and stirred under pressure for 1 hour to carry out the glutarimide cyclization reaction. The liquid temperature was then lowered to 120°C, and the reactor was depressurized to distill off unreacted monomethylamine, methanol, and a portion of mXy, yielding approximately 50% by mass of a mXy solution of glutarimide-cyclized methacrylic acid polymer.

[0602] In this polymerization solution, 0.1% by mass of Irganox 1010 and 0.05% by mass of Irgafos168 relative to 100% by mass of the polymer contained in the solution are added under stirring.

[0603] The polymer solution containing antioxidants is filtered by passing it through a filter with a filtration precision of 2 μm made of SUS316L metal fibers.

[0604] To recover polymer from the polymerization solution, a flat-plate heat exchanger with an internal volume of approximately 0.3 m³ is used as the apparatus for the devolatilization process. This heat exchanger comprises a flat-plate slit-type flow path and a heat medium flow path. 3 A devolatilization device consisting of a pressure-reducing vessel (hereinafter referred to as a devolatilization tank) with an attached SUS heating medium sheath, wherein the devolatilization device does not have a rotating part.

[0605] A solution containing the polymer obtained through polymerization is fed at a rate of 30 L / h to a heat exchanger located at the top of a vacuum vessel. After being heated to 260°C, the solution is fed into a devolatilization tank heated and depressurized to an internal temperature of 260°C and a vacuum degree of 30 Torr for devolatilization treatment. The shear rate within the devolatilization unit is calculated to be 5.3 s based on the device shape and operating conditions. -1 .

[0606] The devolatilized polymer is pressurized from the bottom of the devolatilization tank using a gear pump, extruded from a wire die, water-cooled, and then granulated to obtain a methacrylic resin composition D.

[0607] The composition of the obtained methacrylic resin composition D was confirmed, showing an imidization rate of 3.2% and a glutarimide structural unit content of 5.1% by mass. Additionally, the weight-average molecular weight Mw was 93,000, Mw / Mn was 1.79, Mz / Mw was 1.51, and the glass transition temperature was 122°C.

[0608] [Manufacturing Example 5]

[0609] Except that the amounts of each monomer in the solution prepared in the reactor were set to 39.3 kg of phMI, 46.5 kg of chMI, and 354.2 kg of MMA, the methacrylic resin composition E was obtained in the same manner as in Manufacturing Example 2.

[0610] The composition of the methacrylic resin composition E was confirmed, derived from the structural units of the monomers MMA, phMI, and chMI, which were 83.2% by mass, 7.6% by mass, and 9.2% by mass, respectively. Additionally, the weight-average molecular weight Mw was 143,000, the Mw / Mn ratio was 2.35, the Mz / Mw ratio was 1.81, and the glass transition temperature was 132°C.

[0611] [Manufacturing Comparison Example 1]

[0612] 352.4 kg of an mXy solution with a pH MI of 10.3% (APSI relative to pH MI: 0.42 ppm) after washing and dehydration, and 310.3 kg of an mXy solution with a CH MI of 20.3% (CCSI relative to CH MI: 0.60 ppm) after washing and dehydration, were measured and added to a 1.25 m³ container equipped with a sheathed temperature control device and stirring blades. 3 In a reactor at a solution temperature of 60°C and an internal pressure of 5 kPa, 335.4 kg of mXy was removed by distillation under reduced pressure while stirring. Next, the reactor was restored to atmospheric pressure, and 8.9 kg of mXy was added, thus preparing a mixed solution of 36.3 kg of phMI, 63.0 kg of chMI, and 236.9 kg of mXy. 340.7 kg of MMA and 0.275 kg of n-octylthiol (as a chain transfer agent) were measured, added, and stirred to obtain a monomer mixed solution.

[0613] Next, measure 123.1 kg of mXy and add it to container 1.

[0614] In addition, 110.0 kg of MMA and 90.0 kg of mXy were measured and stirred in tank 2 as a supplementary monomer solution.

[0615] For the liquid contents of the reactor, nitrogen-based bubbling was carried out at a rate of 30 L / min for 1 hour, and for each of tanks 1 and 2, nitrogen-based bubbling was carried out at a rate of 10 L / min for 30 minutes to remove dissolved oxygen.

[0616] Subsequently, steam was blown into the jacket to raise the solution temperature in the reactor to 128°C. While stirring at 50 rpm, a polymerization initiator solution of 0.37 kg of 1,1-di(tert-butylperoxide)cyclohexane dissolved in 3.005 kg of mXy was added at a rate of 1 kg / h to initiate polymerization. 0.5 hours after the start of polymerization, the rate of initiator solution addition was reduced to 0.25 kg / h, while mXy was added from tank 1 at a rate of 35.2 kg / h for 3.5 hours.

[0617] It should be noted that the solution temperature in the reactor is controlled at 128±2℃ during polymerization using sheath-based temperature control.

[0618] Next, 4 hours after the start of polymerization, the rate of initiator solution addition was changed to 0.75 kg / h, while the monomer solution containing MMA was added from tank 2 at a rate of 100.0 kg / h for 2 hours.

[0619] Furthermore, the initiator solution addition rate was reduced to 0.5 kg / h 6 hours after polymerization began, and addition was stopped 7 hours after polymerization began. Polymerization was continued for another hour to obtain a polymerization solution containing a methacrylic resin with ring structural units on the main chain.

[0620] The amount of N-substituted maleimide in the obtained polymerization solution was evaluated, and the results included 220 ppm phMI and 1070 ppm chMI.

[0621] In this polymerization solution, 0.1% by mass of Irganox 1010 and 0.05% by mass of Irgafos168 are added with stirring, relative to 100% by mass of the polymer contained in the solution.

[0622] The polymer solution containing antioxidants is filtered by passing it through a filter with a filtration precision of 2 μm made of SUS316L metal fibers.

[0623] Next, the obtained polymerization solution was introduced into a twin-screw extruder equipped with multiple vents for devolatilization. In the twin-screw extruder, the obtained polymerization solution was supplied at a rate of 10 kg / h (resin conversion), and the conditions were set as follows: barrel temperature 260°C, screw speed 150 rpm, and vacuum degree 10–40 Torr. The resin devolatilized in the twin-screw extruder was extruded from the thread die, water-cooled, and then granulated to obtain a methacrylic resin composition F. The shear rate within the devolatilization unit was calculated to be 80 s based on the device shape and operating conditions. -1 .

[0624] The composition of the methacrylic resin composition F was confirmed, derived from the structural units of the monomers MMA, phMI, and chMI, which were 80.9% by mass, 7.0% by mass, and 12.1% by mass, respectively. Additionally, the weight-average molecular weight Mw was 136,000, the Mw / Mn ratio was 2.35, the Mz / Mw ratio was 1.81, and the glass transition temperature was 134°C.

[0625] [Manufacturing Comparison Example 2]

[0626] Except for preparing a mixed solution of 36.3 kg phMI, 63.0 kg chMI, and 236.9 kg mXy by directly using commercially available products in their unrefined state as phMI and chMI, the same procedure as in Manufacturing Example 2 was performed to obtain the methacrylic resin composition G. The shear rate within the devolatilization unit was calculated to be 5.3 s based on the device shape and operating conditions. -1 .

[0627] It should be noted that the evaluation of the amount of N-substituted maleimide in the obtained polymerization solution includes 220 ppm phMI and 1070 ppm chMI.

[0628] The composition of the obtained particulate polymer was confirmed, derived from the structural units of each monomer, MMA, phMI, and chMI, which were 80.9% by mass, 7.1% by mass, and 12.1% by mass, respectively. Furthermore, the weight-average molecular weight (Mw) was 142,000, the Mw / Mn ratio was 2.32, the Mz / Mw ratio was 1.75, and the glass transition temperature was 134 °C.

[0629] [Manufacturing Comparison Example 3]

[0630] As commercially available products, phMI and chMI were used directly in their unrefined state. 38.6 kg of phMI, 65.7 kg of chMI, 450.0 kg of mXy, 445.7 kg of MMA, and 0.413 kg of n-octylthiol as a chain transfer agent were measured and added to a 1.25 m³ container equipped with a jacket-based temperature control device and stirring blades. 3 The reactor is stirred to obtain a monomer mixture solution.

[0631] For the contents of the reactor liquid, nitrogen-based bubbling is carried out at a rate of 30 L / min for 1 hour to remove dissolved oxygen.

[0632] Subsequently, steam was blown into the sheath to raise the temperature of the solution in the reactor to 125°C. While stirring at 50 rpm, 0.23 kg of 1,1-di(tert-butylperoxy)cyclohexane dissolved in 2.77 kg of mXy polymerization initiator solution was added at a rate of 0.5 kg / h to start polymerization. Addition was stopped 6 hours after the start of polymerization.

[0633] It should be noted that the solution temperature in the reactor is controlled at 125±2℃ using sheath-based temperature regulation during polymerization.

[0634] After 8 hours from the start of polymerization, a polymerization solution containing a methacrylic resin with a ring structure on the main chain is obtained.

[0635] The amount of N-substituted maleimide in the obtained polymerization solution was evaluated, and the results included 1340 ppm phMI and 4390 ppm chMI.

[0636] In this polymerization solution, 0.1% by mass of Irganox 1010 and 0.05% by mass of Irgafos168 relative to 100% by mass of the polymer contained in the solution are added under stirring.

[0637] The polymer solution containing this antioxidant is filtered by passing it through a filter with a filtration precision of 2 μm made of SUS316L metal fibers.

[0638] The polymerization solution containing this antioxidant was fed into a concentration unit consisting of a tubular heat exchanger preheated to 170°C and a vaporization tank, increasing the polymer concentration in the solution to 70% by mass. The resulting polymerization solution was then fed into a heat transfer area of ​​0.2 m². 2 A thin-film evaporator with a rotating section is used for devolatilization.

[0639] The process was carried out under the following conditions: internal temperature 280℃, feed rate 30L / hr, rotation speed 400rpm, and vacuum degree 30Torr. The devolatilized polymer was pressurized using a gear pump, extruded from a wire die, water-cooled, and then granulated to obtain the methacrylic resin composition H. The shear rate inside the thin-film evaporator with the rotating section was calculated to be 3200s based on the device shape and operating conditions. -1 .

[0640] The composition of the obtained particulate polymer was confirmed, derived from the structural units of each monomer, MMA, phMI, and chMI, which were 81.0% by mass, 7.2% by mass, and 11.8% by mass, respectively. Furthermore, the weight-average molecular weight (Mw) was 136,000, the Mw / Mn ratio was 2.21, the Mz / Mw ratio was 1.71, and the glass transition temperature was 134 °C.

[0641] [Manufacturing Comparison Example 4]

[0642] Except that the amounts of each monomer in the solution prepared in the reactor were set to 41.3 kg of phMI, 41.3 kg of chMI, and 357.5 kg of MMA, the process was carried out in the same manner as in Manufacturing Example 2 to obtain methacrylic resin composition I.

[0643] The composition of methacrylic resin composition I was confirmed, derived from the structural units of each monomer, MMA, phMI, and chMI, which were 84.1% by mass, 8.0% by mass, and 7.9% by mass, respectively. Additionally, the weight-average molecular weight (Mw) was 145,000, the Mw / Mn ratio was 2.31, the Mz / Mw ratio was 1.77, and the glass transition temperature was 130°C.

[0644] [Manufacturing Comparison Example 5]

[0645] Polymethyl methacrylate was imidized with monomethylamine using a co-rotating biaxial extruder to obtain a methacrylic resin composition J having glutarimide structural units.

[0646] Specifically, a co-rotating twin-screw extruder with a 40mm screw diameter was used. The extruder barrel temperature was set to 270℃, and the screw speed was set to 150rpm. Polymethyl methacrylate (PMMA) with a weight-average molecular weight (Mw) of 108,000 was supplied at a rate of 20kg / h through the hopper, while nitrogen was introduced into the extruder at a flow rate of 200mL / min. After the resin was melted and filled by the kneading block, 1.8 parts by weight of monomethylamine relative to 100 parts by weight of the raw resin were injected through the nozzle to initiate an imidization reaction. A reverse flight was placed at the end of the reaction zone (near the vent) to fill the zone with resin. The pressure at the vent was reduced to 50 Torr to remove reaction byproducts and excess methylamine. The resin exiting the die at the extruder outlet in a stranded manner was cooled in a water bath and then granulated using a granulator to obtain the imide resin.

[0647] Next, using a co-rotating twin-screw extruder with a screw diameter of 40 mm, the extruder barrel temperature was set to 250°C, the screw speed to 150 rpm, and the obtained imide resin was supplied at a rate of 20 kg / hr. After the resin was melted and filled by a kneading block, a mixture of dimethyl carbonate and triethylamine was injected through a nozzle as an esterifying agent to reduce the carboxylic acid groups in the resin. The ratio of dimethyl carbonate to triethylamine was 3.2 parts by weight relative to 100 parts by weight of imide resin, and 0.8 parts by weight relative to triethylamine. A reverse thread was inserted at the end of the reaction zone to fill the area with resin. The pressure at the vent was reduced to 50 Torr to remove reaction byproducts and excess dimethyl carbonate. The resin exiting from the die at the extruder outlet in a stranded manner was cooled in a water bath and then granulated using a granulator to obtain a methacrylic acid resin composition J with a glutarimide structure.

[0648] The imidization rate of this resin composition is 3.3%, and the content of glutarimide structural units is 5.2% by mass. Based on the device shape and operating conditions, the shear rate within the twin-screw extruder is calculated to be approximately 80 s. -1 .

[0649] In addition, the weight-average molecular weight Mw is 96,000, Mw / Mn is 1.82, Mz / Mw is 1.48, and the glass transition temperature is 122℃.

[0650] [Examples 1-5, Comparative Examples 1-5]

[0651] Using methacrylic resin compositions A to J obtained from the manufacturing examples and comparative examples, light guides were injection molded using the following method, and their properties were measured. The results are shown in Table 1.

[0652] <Molding of Resin-based Light Guides>

[0653] After drying the methacrylic resin compositions A to J in a forced-air circulation dryer at 100°C for 4 hours, the light guide was injection molded using a flat mold with a length of 50 mm, a width of 20 mm, and a thickness of 5 mm, using an injection molding machine with a clamping force of 50 T, a barrel temperature of 270°C, a mold temperature of 90°C, an injection speed of 10 mm / s, a holding pressure of 80 MPa for 20 seconds, and a cooling time of 30 seconds.

[0654] Furthermore, the mixture was annealed for 3 hours in an oven at a temperature set 25°C lower than the glass transition temperature of the methacrylic resin composition.

[0655] [Table 1]

[0656]

[0657] The resin light guide of the present invention can obtain a clear image when forming a head-mounted display, thus contributing to the weight reduction of display devices such as head-mounted displays.

Claims

1. A head-mounted display, the head-mounted display having a resin light guide, characterized in that, The average absolute value of the in-plane phase difference of the resin-made light guide is less than 5 nm. The content of the fluorescent light-emitting substance in the resin-based light guide is 0.1 × 10⁻⁶. -9 ~4.0×10 -9 The concentration (mol / L) was determined using the concentration-intensity conversion formula for the ethanol solution of fluorescein, based on the fluorescence intensity at 530 nm when a 2.0% by mass solution dissolved in chloroform was measured at an excitation wavelength of 436 nm. The resin-based light guide comprises a methacrylic resin. The methacrylic resin comprises a methacrylic resin having structural unit X and structural units derived from methacrylate monomers, wherein structural unit X is a structural unit having a ring structure on the main chain. The structural unit X comprises at least one structural unit selected from the group consisting of structural units derived from N-substituted maleimide monomers, glutarimide structural units, and lactone structural units. The resin light guide directs the image light from the display element through total internal reflection.

Citation Information

Patent Citations

  • Multiilayered polymeric composition

    JP1976129449A

  • Multiilayered polymer compositions

    JP1977056150A

  • Production of impact-resistant acrylic polymer

    JP1984202213A

  • The multilayer structure of the method of manufacturing the acrylic resin molding material

    JP1985017406B2

  • Highly weather-and impact-resistant acrylic resin granular composite material

    JP1988027516A